Li2O-Al2O3-SiO2 crystallized glass

By controlling the content of TiO2 and adjusting the β-OH value, the yellow coloring problem of Li2O-Al2O3-SiO2-based crystallized glass is solved, and the transparency and manufacturing cost of the glass are reduced.

CN116057023BActive Publication Date: 2025-04-15NIPPON ELECTRIC GLASS CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202180062339.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-09-11
Filing Date
2021-09-06
Publication Date
2025-04-15
Estimated Expiration
2041-09-06

AI Technical Summary

Technical Problem

During the manufacturing process, Li2O-Al2O3-SiO2 crystallized glass has yellow coloring problems caused by TiO2, Fe2O3, etc., resulting in a decrease in transparency.

Method used

By controlling the content of TiO2 and increasing the moisture in the glass, the β-OH value is adjusted within the range of 0.001 to 2/mm to ensure sufficient crystallization and transparency of the glass.

Benefits of technology

The yellow coloring caused by TiO2, Fe2O3, etc. is achieved, ensuring the transparency of the glass and reducing the manufacturing cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116057023B_ABST
    Figure CN116057023B_ABST
Patent Text Reader

Abstract

The present invention provides a Li2O-Al2O3-SiO2 crystallized glass which ensures transparency and suppresses yellow coloration caused by TiO2, Fe2O3, etc. The Li2O-Al2O3-SiO2 crystallized glass of the present invention is characterized in that it contains less than 0.5% TiO2 by mass % and has a β-OH value of 0.001 to 2 / mm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to Li2O-Al2O3-SiO2 crystallized glass. Specifically, it relates to a Li2O-Al2O3-SiO2 crystallized glass, which is suitable as a material for high-tech products such as front windows of oil stoves, wood stoves, color filters or image sensor substrates, positioning parts for firing electronic components, light diffusion plates, furnace core tubes for semiconductor manufacturing, masks for semiconductor manufacturing, optical lenses, dimensional measurement parts, communication parts, building parts, chemical reaction containers, electromagnetic cooking top plates, heat-resistant tableware, heat-resistant covers, window glass for fireproof doors, parts for astronomical telescopes, and cosmic optical parts. Background Art

[0002] At present, Li2O-Al2O3-SiO2 crystallized glass is used as a material for the front windows of oil stoves, wood stoves, etc., substrates for high-tech products such as color filters or image sensor substrates, positioning parts for electronic component firing, light diffusion plates, furnace core tubes for semiconductor manufacturing, masks for semiconductor manufacturing, optical lenses, dimensional measurement parts, communication parts, building parts, chemical reaction containers, electromagnetic cooking top plates, heat-resistant tableware, heat-resistant covers, window glass for fireproof doors, parts for astronomical telescopes, and space optical parts. For example, Patent Documents 1 to 3 disclose Li2O-Al2O3-SiO2 crystallized glass formed by precipitation of Li2O-Al2O3-SiO2 crystals such as β-quartz solid solution (Li2O·Al2O3·nSiO2 [where 2≤n≤4]) and β-spodumene solid solution (Li2O·Al2O3·nSiO2 [where n≥4]) as the main crystal.

[0003] Li2O-Al2O3-SiO2 crystallized glass has a low coefficient of thermal expansion and high mechanical strength, so it has excellent thermal properties. In addition, by properly adjusting the heat treatment conditions in the crystallization process, the type of precipitated crystals can be controlled, and transparent crystallized glass (precipitated β-quartz solid solution) can be easily produced.

[0004] However, in the case of manufacturing such crystallized glass, it is necessary to melt at a high temperature exceeding 1400°C. Therefore, As2O3 and Sb2O3 are used as clarifiers added to the glass batch, which generate a large amount of clarification gas when melted at high temperature. However, As2O3 and Sb2O3 are highly toxic and may pollute the environment during the glass manufacturing process or when treating waste glass.

[0005] Therefore, SnO2 and Cl have been proposed as alternative clarifiers to As2O3 and Sb2O3 (see, for example, Patent Documents 4 and 5). However, Cl is likely to corrode molds and metal rollers during glass molding, and as a result, there is a concern that the surface quality of the glass may deteriorate.

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: Japanese Patent Publication No. 39-21049

[0009] Patent Document 2: Japanese Patent Publication No. 40-20182

[0010] Patent Document 3: Japanese Patent Application Laid-Open No. 1-308845

[0011] Patent Document 4: Japanese Patent Application Laid-Open No. 11-228180

[0012] Patent Document 5: Japanese Patent Application Laid-Open No. 11-228181 Summary of the invention

[0013] Technical problem to be solved by the invention

[0014] Moreover, Li2O-Al2O3-SiO2 crystallized glass has coloration caused by TiO2, Fe2O3, etc., and has the problem of yellowing and poor appearance. In order to improve the yellow coloration of transparent crystallized glass, the content of TiO2 can be reduced, but when the content of TiO2 is reduced, the rate of crystal nucleation in the crystallization process slows down, and the amount of crystal nucleus generated tends to decrease. As a result, coarse crystals increase, making the crystallized glass turbid, which is easy to damage transparency.

[0015] An object of the present invention is to provide a Li2O-Al2O3-SiO2-based crystallized glass which ensures transparency and suppresses yellow coloration caused by TiO2, Fe2O3, etc.

[0016] Technical solutions for solving technical problems

[0017] The inventors of the present invention have found that the insufficient amount of crystal nucleation associated with a decrease in the TiO2 content can be compensated by containing more water.

[0018] The Li2O-Al2O3-SiO2 crystallized glass of the present invention is characterized in that it contains 0% or more and less than 0.5% TiO2 by mass %, and the β-OH value of the crystallized glass is 0.001 to 2 / mm. By making the β-OH value 0.001 / mm or more, even if the TiO2 content is reduced to less than 0.5% in order to improve the yellow coloration, the glass can be fully crystallized. "β-OH value" refers to the value obtained by the following formula after measuring the transmittance of the glass by FT-IR.

[0019] β-OH value = (1 / X)log(T1 / T2)

[0020] X: Glass thickness (mm)

[0021] T1: at reference wavelength 3846cm -1 Transmittance (%)

[0022] T2: hydroxyl absorption wavelength 3600cm -1 Minimum transmittance near (%)

[0023] The Li2O-Al2O3-SiO2 crystallized glass of the present invention preferably also contains, by mass%, 40 to 90% SiO2, 5 to 30% Al2O3, 1 to 10% Li2O, 0 to 20% SnO2, 1 to 20% ZrO2, 0 to 10% MgO, 0 to 10% P2O5, and more than 0% and less than 2% Sb2O3 + As2O3.

[0024] As described above, by making the β-OH value less than 2 / mm, the glass can be sufficiently clarified even if the total amount of the clarifiers Sb2O3 and As2O3 is reduced to less than 2%. In addition, "Sb2O3+As2O3" refers to the total amount of Sb2O3 and As2O3.

[0025] The Li2O-Al2O3-SiO2 system crystallized glass of the present invention preferably also contains, by mass%, 0 to 10% Na2O, 0 to 10% K2O, 0 to 10% CaO, 0 to 10% SrO, 0 to 10% BaO, 0 to 10% ZnO, and 0 to 10% B2O3.

[0026] The Li2O-Al2O3-SiO2-based crystallized glass of the present invention preferably further contains 0.1% or less of Fe2O3 in terms of mass%.

[0027] The Li2O-Al2O3-SiO2 crystallized glass of the present invention preferably has a mass ratio of SnO2 / (SnO2+ZrO2+P2O5+TiO2+B2O3) of 0.06 or more. Here, "SnO2 / (SnO2+ZrO2+P2O5+TiO2+B2O3)" refers to the value obtained by dividing the content of SnO2 by the total amount of SnO2, ZrO2, P2O5, TiO2 and B2O3.

[0028] The Li2O-Al2O3-SiO2 crystallized glass of the present invention preferably has a mass ratio of Al2O3 / (SnO2+ZrO2) of 7.1 or less. Here, "Al2O3 / (SnO2+ZrO2)" refers to the value obtained by dividing the content of Al2O3 by the total amount of SnO2 and ZrO2.

[0029] The Li2O-Al2O3-SiO2 crystallized glass of the present invention preferably has a mass ratio of SnO2 / (SnO2+ZrO2) of 0.01 to 0.99. Here, "SnO2 / (SnO2+ZrO2)" refers to the value obtained by dividing the content of SnO2 by the total amount of SnO2 and ZrO2.

[0030] The Li2O-Al2O3-SiO2-based crystallized glass of the present invention preferably contains 8% or less of Na2O+K2O+CaO+SrO+BaO by mass %, wherein "Na2O+K2O+CaO+SrO+BaO" refers to the total amount of Na2O, K2O, CaO, SrO and BaO.

[0031] The Li2O-Al2O3-SiO2 crystallized glass of the present invention preferably has a mass ratio of (SiO2+Al2O3) / Li2O of 20 or more. Here, "(SiO2+Al2O3) / Li2O" refers to the value obtained by dividing the total amount of SiO2 and Al2O3 by the content of Li2O.

[0032] The Li2O-Al2O3-SiO2 crystallized glass of the present invention preferably has a mass ratio of (SiO2+Al2O3) / SnO2 of 44 or more. Here, "(SiO2+Al2O3) / SnO2" refers to the value obtained by dividing the total amount of SiO2 and Al2O3 by the content of SnO2.

[0033] The Li2O-Al2O3-SiO2 crystallized glass of the present invention preferably has a mass ratio of (MgO+ZnO) / Li2O less than 0.395 or greater than 0.754. Here, "(MgO+ZnO) / Li2O" refers to the value obtained by dividing the total amount of MgO and ZnO by the content of Li2O.

[0034] The Li2O-Al2O3-SiO2 crystallized glass of the present invention preferably has a mass ratio of (Li2O+Na2O+K2O) / ZrO2 of 2.0 or less. Here, "(Li2O+Na2O+K2O) / ZrO2" refers to the value obtained by dividing the total amount of Li2O, Na2O and K2O by the content of ZrO2.

[0035] The Li2O-Al2O3-SiO2 crystallized glass of the present invention preferably has a TiO2 / ZrO2 mass ratio of 0.0001 to 5.0, wherein "TiO2 / ZrO2" refers to a value obtained by dividing the TiO2 content by the ZrO2 content.

[0036] The Li2O-Al2O3-SiO2 crystallized glass of the present invention preferably has a mass ratio of TiO2 / TiO2+Fe2O3 of 0.001 to 0.999, wherein "TiO2 / (TiO2+Fe2O3)" refers to the value obtained by dividing the content of TiO2 by the total amount of TiO2 and Fe2O3.

[0037] The Li2O-Al2O3-SiO2-based crystallized glass of the present invention preferably contains less than 0.05% of HfO2+Ta2O5 by mass %, wherein "HfO2+Ta2O5" refers to the total amount of HfO2 and Ta2O5.

[0038] The Li 2 O—Al 2 O 3 —SiO 2 -based crystallized glass of the present invention preferably contains 7 ppm or less of Pt in terms of mass %.

[0039] The Li 2 O—Al 2 O 3 —SiO 2 -based crystallized glass of the present invention preferably contains 7 ppm or less of Rh in terms of mass %.

[0040] The Li2O-Al2O3-SiO2-based crystallized glass of the present invention preferably contains 9 ppm or less of Pt+Rh in terms of mass %, wherein "Pt+Rh" refers to the total amount of Pt and Rh.

[0041] The Li2O-Al2O3-SiO2-based crystallized glass of the present invention is preferably colorless and transparent in appearance.

[0042] The Li2O-Al2O3-SiO2 crystallized glass of the present invention preferably has a transmittance of 10% or more at a thickness of 3 mm and a wavelength of 300 nm, and can therefore be well used in various applications requiring ultraviolet transmittance.

[0043] The Li2O-Al2O3-SiO2-based crystallized glass of the present invention preferably has β-quartz solid solution precipitated as a main crystal, thereby making it easy to obtain crystallized glass with a low thermal expansion coefficient.

[0044] The Li2O-Al2O3-SiO2 crystallized glass of the present invention preferably has a thermal expansion coefficient of 30×10 -7 / °C or less. Therefore, it can be suitably used in various applications requiring low expansion properties.

[0045] The Li2O-Al2O3-SiO2 crystallized glass of the present invention preferably has a thermal expansion coefficient of 30×10 -7 / °C or less. Therefore, it can be suitably used in various applications requiring low expansion properties in a wide temperature range.

[0046] The Li2O-Al2O3-SiO2 crystallized glass of the present invention preferably has a transmittance change rate of 50% or less before and after crystallization when the thickness is 3 mm and the wavelength is 300 nm. Wherein, "transmittance change rate before and after crystallization" refers to {(transmittance before crystallization (%) - transmittance after crystallization (%)) / transmittance before crystallization (%)} × 100 (%).

[0047] The Li2O-Al2O3-SiO2-based crystallized glass of the present invention is preferably calculated on a mass ratio basis, wherein Al2O3 / (Li2O+(1 / 2×(MgO+ZnO)) is 3.0 to 8.0. “Al2O3 / (Li2O+(1 / 2×(MgO+ZnO)” refers to the value obtained by dividing the Al2O3 content by the sum of the Li2O content and half of the total amount of MgO and ZnO.

[0048] The Li2O-Al2O3-SiO2-based crystallized glass of the present invention is characterized by containing more than 0% of MoO3 by mass %, and having a β-OH value of 0.001 to 0.5 / mm.

[0049] Effects of the Invention

[0050] According to the present invention, it is possible to provide a Li 2 O—Al 2 O 3 —SiO 2 -based crystallized glass in which transparency is ensured and yellow coloration due to TiO 2 , Fe 2 O 3 , and the like is suppressed. BRIEF DESCRIPTION OF THE DRAWINGS

[0051] Figure 1 This is the transmittance curve of sample No. 27 before crystallization.

[0052] Figure 2 This is the transmittance curve of sample No. 27 after crystallization.

[0053] Figure 3 This is a graph showing the relationship between the β-OH value and the density of samples A to E.

[0054] Figure 4 This is a graph showing the relationship between the β-OH value and the density of samples F to J.

[0055] Figure 5 This is a graph showing the relationship between the β-OH value and the density of samples K to M. DETAILED DESCRIPTION

[0056] The Li2O-Al2O3-SiO2 crystallized glass of the present invention is characterized in that it contains less than 0.5% of TiO2 by mass %, and the β-OH value of the crystallized glass is 0.001 to 2 / mm.

[0057] First, the glass composition of the Li2O-Al2O3-SiO2-based crystallized glass of the present invention is described. In the following description of the content of each component, "%" means "mass %" unless otherwise specified.

[0058] TiO2 is a nucleating component for precipitating crystals in the crystallization process. On the other hand, when it is contained in large quantities, the coloring of the glass becomes significantly stronger. In particular, although the zirconium titanate-based crystals containing ZrO2 and TiO2 act as crystal nuclei, the electrons jump (LMCT transition) from the valence band of oxygen as a ligand to the conduction band of zirconium and titanium as central metals, participating in the coloring of the crystallized glass. In addition, when titanium remains in the residual glass phase, it is possible that LMCT transition occurs from the valence band of the SiO2 skeleton to the conduction band of the 4-valent titanium of the residual glass phase. In addition, in the 3-valent titanium of the residual glass phase, d-d transition occurs, participating in the coloring of the crystallized glass. Furthermore, when titanium and iron coexist, ilmenite (FeTiO3)-like coloring occurs. It is also known that the yellow color becomes stronger when titanium and tin coexist. Therefore, the content of TiO2 is preferably 0% or more and less than 0.5%, 0-0.48%, 0-0.46%, 0-0.44%, 0-0.42%, 0-0.4%, 0-0.38%, 0-0.36%, 0-0.34%, 0-0.32%, 0-0.3%, 0-0.28%, 0-0.26%, 0-0.24%, 0-0.22%, 0-0.2%, 0-0.18%, 0-0.16%, 0-0.14%, 0-0.12%, particularly preferably 0-0.1%. However, since TiO2 is easily mixed in as an impurity, if TiO2 is to be completely removed, there is a tendency that the raw material batch becomes expensive and the manufacturing cost increases. In order to suppress an increase in manufacturing cost, the lower limit of the TiO2 content is preferably 0.0003% or more, 0.0005% or more, 0.001% or more, 0.005% or more, 0.01% or more, and particularly preferably 0.02% or more.

[0059] The Li2O-Al2O3-SiO2-based crystallized glass of the present invention may contain the following components in addition to the above components in the glass composition.

[0060] SiO2 is a component that forms the skeleton of glass and constitutes Li2O-Al2O3-SiO2 system crystals. The content of SiO2 is preferably 40-90%, 52-80%, 55-75%, 56-70%, 59-70%, 60-70%, 60-69.5%, 60.5-69.5%, 61-69.5%, 61.5-69.5%, 62-69.5%, 62.5-69.5%, 63-69.5%, and 63.5-69.5% is particularly preferred. When the content of SiO2 is too small, there is a tendency for the thermal expansion coefficient to increase, and it becomes difficult to obtain a crystallized glass with excellent thermal shock resistance. In addition, there is a tendency for chemical durability to decrease. On the other hand, when the content of SiO2 is too much, the solubility of the glass decreases or the viscosity of the glass melt increases, it becomes difficult to clarify or the glass molding becomes difficult, and it is easy to reduce productivity. Furthermore, the time required for crystallization becomes longer, and productivity tends to decrease.

[0061] Al2O3 is a component that forms the skeleton of glass and constitutes Li2O-Al2O3-SiO2 system crystals. In addition, Al2O3 is a component that is coordinated around the crystal nucleus to form a core-shell structure. Due to the existence of the core-shell structure, it is difficult to supply the crystal nucleus component from the outside of the shell. Therefore, the crystal nucleus is difficult to enlarge and it is easy to form multiple tiny crystal nuclei. The content of Al2O3 is preferably 5-30%, 8-30%, 9-28%, 10-27%, 12-27%, 14-27%, 16-27%, 17-27%, 18-27%, 18-27%, 18-26.5%, 18.1-26.5%, 19-26.5%, 19.5-26.5%, 20-26.5%, 20.5-26.5%, and particularly preferably 20.8-25.8%. When Al2O3 content is too little, there is a tendency that the coefficient of thermal expansion becomes high, and it becomes difficult to obtain the crystallized glass with excellent thermal shock resistance. In addition, there is a tendency that chemical durability reduces. And, the crystal nucleus becomes large, and crystallized glass is prone to white turbidity. On the other hand, when Al2O3 content is too much, the melting property of glass reduces or the viscosity of glass melt becomes high, and it becomes difficult to clarify or the molding of glass becomes difficult, and productivity is easily reduced. There is also a tendency that the crystallization of mullite is separated out and the glass is devitrified, and crystallized glass is easily damaged.

[0062] Li2O is a component that constitutes Li2O-Al2O3-SiO2 crystals, and has a great influence on crystallinity, and reduces the viscosity of glass, improving the meltability and formability of glass. The content of Li2O is preferably 1-10%, 2-10%, 2-8%, 2.5-6%, 2.8-5.5%, 2.8-5%, 3-5%, 3-4.5%, 3-4.2%, and particularly preferably 3.2-4%. When the content of Li2O is too low, there is a tendency for mullite crystals to precipitate and cause the glass to lose clarity. In addition, when the glass is crystallized, it becomes difficult to precipitate Li2O-Al2O3-SiO2 crystals, and it is difficult to obtain crystallized glass with excellent heat shock resistance. Moreover, the meltability of the glass decreases or the viscosity of the glass melt increases, making it difficult to clarify or difficult to form the glass, which easily reduces productivity. On the other hand, when the content of Li2O is too high, the crystallinity becomes too strong, the glass tends to be easily devitrified, and the crystallized glass becomes easily broken.

[0063] SiO2, Al2O3, and Li2O are the main components of the β-quartz solid solution as the main crystal. Li2O and Al2O3 are dissolved in the SiO2 skeleton by compensating each other's charges. By containing these three components in a suitable ratio, crystallization can be carried out efficiently and low-cost manufacturing can be achieved. (SiO2+Al2O3) / Li2O is preferably 20 or more, 20.2 or more, 20.4 or more, 20.6 or more, 20.8 or more, and particularly preferably 21 or more in terms of mass ratio.

[0064] SnO2 is a component that acts as a clarifier. Moreover, it is also a necessary component for the efficient precipitation of crystals in the crystallization process. On the other hand, it is also a component that significantly strengthens the coloring of the glass when contained in large quantities. The content of SnO2 is preferably 0-20%, more than 0% and less than 20%, 0.05-20%, 0.1-10%, 0.1-5%, 0.1-4%, 0.1-3%, 0.15-3%, 0.2-3%, 0.2-2.7%, 0.2-2.4%, 0.25-2.4%, 0.3-2.4%, 0.35-2.4%, 0.4-2.4%, 0.45-2.4%, 0.5- SnO2 has a crystalline structure of 0.2-1.0 % SnO2 and a crystalline structure of 0.2-1.0 % SnO2. The crystalline structure of the glass is preferably 0.2.4%, 0.5-2.35%, 0.5-2.3%, 0.5-2.2%, 0.5-2.1%, 0.5-2.05%, 0.5-2%, 0.5-1.95%, 0.5-1.93%, 0.5-1.91%, 0.5-1.9%, 0.5-1.88%, 0.5-1.85%, 0.5-1.83%, 0.5-1.81%, and 0.5-1.8% is particularly preferred. When the content of SnO2 is too little, the clarification of the glass becomes difficult and the productivity is easily reduced. In addition, there is a concern that sufficient crystal nuclei cannot be formed, and coarse crystals are precipitated to make the glass turbid or damaged. On the other hand, when the content of SnO2 is too much, there is a concern that the coloring of the crystallized glass becomes stronger. In addition, there is a tendency that the evaporation amount of SnO2 during melting increases, and the environmental load increases.

[0065] ZrO2 is a nucleating component for precipitating crystals in the crystallization process. The content of ZrO2 is preferably 1-20%, 1-15%, 1-10%, 1-5%, 1.5-5%, 1.75-4.5%, 1.75-4.4%, 1.75-4.3%, 1.75-4.2%, 1.75-4.1%, 1.75-4%, 1.8-4%, 1.85-4%, 1.9-4%, 1.95-4%, 2-4%, 2.05-4 %, 2.1~4%, 2.15~4%, 2.2~4%, 2.25~4%, 2.3~4%, 2.3~3.95%, 2.3~3.9%, 2.3~3.95%, 2.3~3.9%, 2.3~3.85%, 2.3~3.8%, more than 2.7% and less than 3.8%, 2.8~3.8%, 2.9~3.8%, particularly preferably 3~3.8%. When the content of ZrO2 is too little, there is a concern that sufficient crystal nuclei cannot be formed, coarse crystals are precipitated, and the crystallized glass becomes cloudy or damaged. On the other hand, when the content of ZrO2 is too much, coarse ZrO2 crystals are precipitated, and the glass becomes easy to lose transparency, or the crystallized glass becomes easy to break.

[0066] TiO2 and ZrO2 are components that play the function of crystal nucleus respectively. Ti and Zr are elements of the same family, and their electronegativity and ionic radius are similar. Therefore, as oxides, they are easy to have similar molecular conformations, and it is known that in the coexistence of TiO2 and ZrO2, phase separation is easy to occur in the early stage of crystallization. Therefore, within the allowable range of coloring, TiO2 / ZrO2 is preferably 0.0001-5.0, 0.0001-4.0, 0.0001-3.0, 0.0001-2.5, 0.0001-2.0, 0.0001-1.5, 0.0001-1.0, 0.0001-0.5, 0.0001-0.4 in terms of mass ratio, and 0.0001-0.3 is particularly preferred. When TiO2 / ZrO2 is too small, there is a tendency that the raw material batch becomes expensive and the manufacturing cost increases. When TiO2 / ZrO2 is too large, the rate of nucleation slows down and the manufacturing cost may increase.

[0067] SnO2+ZrO2 is preferably 1-30%, 1.1-30%, 1.1-27%, 1.1-24%, 1.1-21%, 1.1-20%, 1.1-17%, 1.1-14%, 1.1-11%, 1.1-9%, 1.1-7.5%, 1.4-7.5%, 1.8-7.5%, 2.0-7.5%, 2.2-7%, 2.2-6.4%, 2.2-6.2%, 2.2-6%, 2.3-6%, 2.4-6%, 2.5-6%, and 2.8-6% is particularly preferred. When SnO2+ZrO2 is too little, it becomes difficult to precipitate crystal nuclei and crystallize. When SnO2+ZrO2 is too much, the crystal nuclei become larger and the crystallized glass is prone to white turbidity.

[0068] SnO2 has the effect of promoting phase separation in glass. In order to suppress the liquidus temperature to a low level (suppress the risk of devitrification caused by the precipitation of the primary phase), and to make phase separation occur efficiently, and to rapidly nucleate and crystallize in the subsequent steps, the mass ratio of SnO2 / (SnO2+ZrO2) is preferably 0.01-0.99, 0.01-0.98, 0.01-0.94, 0.01-0.90, 0.01-0.86, 0.01-0.82, 0.01-0.78, 0.01-0.74, 0.01-0.70, 0.03-0.70, and particularly preferably 0.05-0.70.

[0069] In addition, SnO2 reacts SnO2→SnO+1 / 2O2 at high temperature, releasing O2 gas into the glass melt. This reaction is known as the clarification mechanism of SnO2, but the O2 gas released during the reaction not only has a "degassing effect" that enlarges the fine bubbles present in the glass melt and releases them outside the glass system, but also has a "stirring effect" that mixes the glass melt. In the Li2O-Al2O3-SiO2 system crystallized glass of the present invention, the content of SiO2 and Al2O3 accounts for more than half. Since these components are insoluble, in order to efficiently form a homogeneous glass melt, these three components need to be contained in a suitable ratio. (SiO2+Al2O3) / SnO2 is preferably 44 or more, 44.3 or more, 44.7 or more, 45 or more, and 45.2 or more in terms of mass ratio. 45.4 or more, 45.6 or more, 45.8 or more, and 46 or more is particularly preferred.

[0070] Al2O3 / (SnO2+ZrO2) is preferably 7.1 or less, 7.05 or less, 7.0 or less, 6.95 or less, 66.9 or less, 6.85 or less, 6.8 or less, 6.75 or less, 6.7 or less, 6.65 or less, 6.6 or less, 6.55 or less, 6.5 or less, 6.45 or less, 6.4 or less, 6.35 or less, 6.3 or less, 6.25 or less, 6.2 or less, 6.15 or less, 6.1 or less, 6.05 or less, 6.0 or less, 5.98 or less, 5.95 or less, 5.92 or less, 5.9 or less, 5.8 or less, 5.7 or less, 5.6 or less, and particularly preferably 5.5 or less. When Al2O3 / (SnO2+ZrO2) is too large, nucleation cannot be carried out efficiently, and efficient crystallization is difficult. If Al2O3 / (SnO2+ZrO2) is too small, the crystal nucleus becomes larger and the crystallized glass tends to become cloudy. Therefore, the lower limit of Al2O3 / (SnO2+ZrO2) is preferably 0.01 or more.

[0071] MgO is dissolved in Li2O-Al2O3-SiO2 system crystals and is a component that increases the thermal expansion coefficient of Li2O-Al2O3-SiO2 system crystals. The content of MgO is preferably 0-10%, 0-8%, 0-6%, 0-5%, 0-4.5%, 0-4%, 0-3.5%, 0.02-3.5%, 0.05-3.5%, 0.08-3.5%, 0.1-3.5%, 0.1-3.3%, 0.1-3%, 0.13-3%, 0.15-3%, 0.17-3%, 0.19-3%, 0.2-2.9%, 0.2-2.7%, 0.2-2.5%, 0.2-2.3%, 0.2-2.2%, 0.2-2.1%, and particularly preferably 0.2-2%. When the content of MgO is too little, there is the tendency that the coefficient of thermal expansion becomes too low. In addition, volume shrinkage can occur when crystallization is separated out, and the amount of this volume shrinkage becomes too large sometimes. In addition, the coefficient of thermal expansion difference of the crystalline phase after the crystallization and the residual glass phase becomes large, so crystallized glass becomes easy to break sometimes. When the content of MgO is too much, crystallinity becomes too strong and becomes easy to devitrify, and crystallized glass becomes easy to break. In addition, there is the tendency that the coefficient of thermal expansion becomes too high.

[0072] P2O5 is a component that inhibits the precipitation of coarse ZrO2 crystals. The content of P2O5 is preferably 0-10%, 0-8%, 0-6%, 0-5%, 0-4%, 0-3.5%, 0.02-3.5%, 0.05-3.5%, 0.08-3.5%, 0.1-3.5%, 0.1-3.3%, 0.1-3%, 0.13-3%, 0.15-3%, 0.17-3%, 0.19-3%, 0.2-2.9%, 0.2-2.7%, 0.2-2.5%, 0.2-2.3%, 0.2-2.2%, 0.2-2.1%, 0.2-2%, and particularly preferably 0.3-1.8%. When the content of P2O5 is too low, coarse ZrO2 crystals are easily precipitated, making the glass easily devitrified, and the crystallized glass may become easily broken. When the content of P2O5 is too high, the amount of Li2O-Al2O3-SiO2 crystals precipitated decreases, and there is a tendency for the thermal expansion coefficient to increase.

[0073] Na2O is a component that can be dissolved in Li2O-Al2O3-SiO2 system crystals, has a great influence on crystallinity, reduces the viscosity of glass, and improves the meltability and formability of glass. In addition, it is also a component used to adjust the thermal expansion coefficient and refractive index of crystallized glass. The content of Na2O is preferably 0-10%, 0-8%, 0-6%, 0-5%, 0-4.5%, 0-4%, 0-3.5%, 0-3%, 0-2.7%, 0-2.4%, 0-2.1%, 0-1.8%, and particularly preferably 0-1.5%. When the content of Na2O is too much, the crystallinity becomes too strong, the glass becomes easy to lose transparency, and the crystallized glass becomes easy to break. In addition, the ionic radius of Na cations is larger than the constituent components of the main crystal, such as Li cations and Mg cations, and it is not easy to enter the crystal, so the Na cations after crystallization are easy to remain in the residual glass (glass matrix). Therefore, when the content of Na2O is too much, there is a tendency that the refractive index difference between the crystalline phase and the residual glass is easily generated, and the crystallized glass is easily turbid. However, since Na2O is easily mixed in as an impurity, if Na2O is to be completely removed, there is a tendency that the raw material batch becomes expensive and the manufacturing cost increases. In order to suppress the increase in manufacturing cost, the lower limit of the Na2O content is preferably 0.0003% or more, 0.0005% or more, and particularly preferably 0.001% or more.

[0074] K2O is a component that can be dissolved in Li2O-Al2O3-SiO2 crystals, has a great influence on crystallinity, reduces the viscosity of glass, and improves the meltability and formability of glass. In addition, it is also a component used to adjust the thermal expansion coefficient and refractive index of crystallized glass. The content of K2O is preferably 0-10%, 0-8%, 0-6%, 0-5%, 0-4.5%, 0-4%, 0-3.5%, 0-3%, 0-2.7%, 0-2.4%, 0-2.1%, 0-1.8%, 0-1.5%, 0-1.4%, 0-1.3%, 0-1.2%, 0-1.1%, 0-1%, 0-0.9%, and particularly preferably 0.1-0.8%. When the content of K2O is too much, the crystallinity becomes too strong, the glass becomes easy to lose clarity, and the crystallized glass becomes easy to break. In addition, the ionic radius of K cations is larger than the constituent components of the main crystal, such as Li cations and Mg cations, and it is not easy to enter the crystallization, so the K cations after crystallization are likely to remain in the residual glass. Therefore, when the content of K2O is too much, there is a tendency that the refractive index difference between the crystalline phase and the residual glass is easily generated, and the crystallized glass is prone to white turbidity. However, since K2O is easily mixed in as an impurity, if K2O is to be completely removed, there is a tendency that the raw material batch becomes expensive and the manufacturing cost increases. In order to suppress the increase in manufacturing cost, the lower limit of the K2O content is preferably 0.0003% or more, 0.0005% or more, and particularly preferably 0.001% or more.

[0075] Li2O, Na2O, K2O are components that improve the meltability and formability of glass, but when the content of these components is too much, there is a concern that the low-temperature viscosity decreases excessively and the glass flows excessively during crystallization. In addition, Li2O, Na2O, K2O are components that may deteriorate the weather resistance, water resistance, and chemical resistance of the glass before crystallization. When the glass before crystallization deteriorates due to moisture, etc., there is a concern that it is difficult to obtain the desired crystallization behavior and the desired characteristics. On the other hand, ZrO2 is a component that plays the role of a nucleating agent, which has the effect of preferential crystallization in the initial stage of crystallization and suppressing the flow of residual glass. In addition, ZrO2 can efficiently fill the interstitial part of the glass network based on SiO2 skeleton, has the effect of hindering the diffusion of protons and various drug components in the glass network, and can improve the weather resistance, water resistance, and chemical resistance of the glass before crystallization. In order to obtain a crystallized glass of the desired shape and characteristics, (Li2O+Na2O+K2O) / ZrO2 should be properly controlled. The mass ratio of (Li2O+Na2O+K2O) / ZrO2 is preferably 2.0 or less, 1.98 or less, 1.96 or less, 1.94 or less, 1.92 or less, and particularly preferably 1.90 or less.

[0076] CaO is a component that reduces the viscosity of glass and improves the meltability and formability of glass. In addition, it is also a component that adjusts the thermal expansion coefficient and refractive index of crystallized glass. The content of CaO is preferably 0-10%, 0-8%, 0-6%, 0-5%, 0-4.5%, 0-4%, 0-3.5%, 0-3%, 0-2.7%, 0-2.4%, 0-2.1%, 0-1.8%, and particularly preferably 0-1.5%. When the content of CaO is too much, the glass becomes easy to lose clarity and the crystallized glass becomes easy to break. In addition, the ionic radius of the Ca cation is larger than the constituent components of the main crystal, such as Li cations and Mg cations, and it is not easy to enter the crystallization, so the Ca cation after crystallization is easy to remain in the residual glass. Therefore, when the content of CaO is too much, there is a tendency that the refractive index difference between the crystal phase and the residual glass is easy to be generated, and the crystallized glass is easy to be turbid. However, since CaO is easily mixed in as an impurity, if you want to completely remove CaO, there is a tendency that the raw material batch becomes expensive and the manufacturing cost increases. In order to suppress an increase in production cost, the lower limit of the CaO content is preferably 0.0001% or more, 0.0003% or more, and particularly preferably 0.0005% or more.

[0077] SrO is a component that reduces the viscosity of glass and improves the meltability and formability of glass. In addition, it is also a component that adjusts the thermal expansion coefficient and refractive index of crystallized glass. The content of SrO is preferably 0-10%, 0-8%, 0-6%, 0-5%, 0-4.5%, 0-4%, 0-3.5%, 0-3%, 0-2.7%, 0-2.4%, 0-2.1%, 0-1.8%, 0-1.5%, and particularly preferably 0-1%. When the content of SrO is too much, the glass becomes easily devitrified and the crystallized glass becomes easily broken. In addition, the ionic radius of the Sr cation is larger than the constituent components of the main crystal, such as Li cations and Mg cations, and it is not easy to enter the crystallization. Therefore, the Sr cation after crystallization is easy to remain in the residual glass. Therefore, when the content of SrO is too much, there is a tendency that the refractive index difference between the crystalline phase and the residual glass is easy to be generated, and the crystallized glass is easy to be turbid. However, since SrO is easily mixed as an impurity, if SrO is completely removed, the raw material batch becomes expensive and the manufacturing cost tends to increase. In order to suppress the increase in manufacturing cost, the lower limit of the SrO content is preferably 0.0001% or more, 0.0003% or more, and particularly preferably 0.0005% or more.

[0078] BaO is a component that reduces the viscosity of glass and improves the meltability and formability of glass. In addition, it is also a component that adjusts the thermal expansion coefficient and refractive index of crystallized glass. The content of BaO is preferably 0-10%, 0-8%, 0-6%, 0-5%, 0-4.5%, 0-4%, 0-3.5%, 0-3%, 0-2.7%, 0-2.4%, 0-2.1%, 0-1.8%, 0-1.5%, and particularly preferably 0-1%. When the content of BaO is too much, crystals containing Ba are precipitated, the glass becomes easily devitrified, and the crystallized glass becomes easily broken. In addition, the ionic radius of Ba cations is larger than the constituent components of the main crystal, such as Li cations and Mg cations, and it is not easy to enter the crystallization, so the Ba cations after crystallization are easily left in the residual glass. Therefore, when the content of BaO is too much, there is a tendency that the refractive index difference between the crystalline phase and the residual glass is easily generated, and the crystallized glass is easily turbid. However, since BaO is easily mixed as an impurity, if BaO is completely removed, the raw material batch becomes expensive and the manufacturing cost tends to increase. In order to suppress the increase in manufacturing cost, the lower limit of the BaO content is preferably 0.0001% or more, 0.0003% or more, and particularly preferably 0.0005% or more.

[0079] MgO, CaO, SrO, BaO are components that improve the meltability and formability of glass, but when the content of these components is too much, there is a concern that the low-temperature viscosity will drop excessively and the glass will flow excessively during crystallization. On the other hand, ZrO2 is a component that functions as a nucleating agent, and has the effect of preferentially crystallizing at the initial stage of crystallization and inhibiting the flow of residual glass. In order to obtain a crystallized glass of the desired shape and characteristics, (MgO+CaO+SrO+BaO) / ZrO2 should be appropriately controlled. (MgO+CaO+SrO+BaO) / ZrO2 is preferably 0-3, 0-2.8, 0-2.6, 0-2.4, 0-2.2, 0-2.1, 0-2, 0-1.8, 0-1.7, 0-1.6 in terms of mass ratio, and particularly preferably 0-1.5.

[0080] Na2O, K2O, CaO, SrO, and BaO are likely to remain in the residual glass after crystallization. Therefore, when their combined amount is too much, it is easy to produce a refractive index difference between the crystalline phase and the residual glass, and the crystallized glass is prone to white turbidity. Therefore, Na2O+K2O+CaO+SrO+BaO is preferably less than 8%, less than 7%, less than 6%, less than 5%, less than 4.5%, less than 4%, less than 3.5%, less than 3%, less than 2.7%, less than 2.42%, less than 2.415%, less than 2.410%, less than 2.405%, and particularly preferably less than 2.4%.

[0081] Li2O, Na2O, K2O, MgO, CaO, SrO, and BaO are components that improve the solubility and formability of glass. In addition, the viscosity (viscosity curve) of a glass melt containing more MgO, CaO, SrO, and BaO tends to change slowly with respect to temperature, and the above-mentioned change of a glass melt containing more Li2O, Na2O, and K2O tends to become steep. When the change of the viscosity curve is too slow, the glass will flow even after being formed into a predetermined shape, and it will be difficult to obtain the desired shape. When the change of the viscosity curve is too steep, the glass melt will solidify in the middle of forming, and it will be difficult to obtain the desired shape. Therefore, (MgO+CaO+SrO+BaO) / (Li2O+Na2O+K2O) should be appropriately controlled. The mass ratio of (MgO+CaO+SrO+BaO) / (Li2O+Na2O+K2O) is preferably 0-2, 0-1.8, 0-1.5, 0-1.2, 0-1, 0-0.9, 0-0.8, 0-0.7, 0-0.6, 0-0.5, and particularly preferably 0-0.45.

[0082] ZnO is a component that is solid-dissolved in Li2O-Al2O3-SiO2 system crystals and has a great influence on crystallinity. In addition, it is also a component used to adjust the thermal expansion coefficient and refractive index of crystallized glass. The content of ZnO is preferably 0-10%, 0-8%, 0-6%, 0-5%, 0-4.5%, 0-4%, 0-3.5%, 0-3%, 0-2.7%, 0-2.4%, 0-2.1%, 0-1.8%, 0-1.5%, and 0-1% is particularly preferred. When the content of ZnO is too much, the crystallinity becomes too strong and it is easy to lose clarity, and the glass becomes easy to break. However, since ZnO is easily mixed as an impurity, if you want to completely remove ZnO, there is a tendency that the raw material batch becomes expensive and the manufacturing cost increases. In order to suppress the increase in manufacturing costs, the lower limit of the ZnO content is preferably 0.0001% or more, 0.0003% or more, and 0.0005% or more is particularly preferred.

[0083] In Li2O-Al2O3-SiO2 crystallized glass, Li cations, Mg cations, and Zn cations are components that are easily dissolved in β-quartz solid solution. These cations are dissolved in the crystal in the form of charge-compensating Al cations. Specifically, it can be considered that In such a form of solid solution, the ratio of Al cations to Li cations, Mg cations, and Zn cations affects the stability of the β-quartz solid solution. In the composition described in the present invention, a crystallized glass can be stably obtained, and in order to make the crystallized glass close to colorless, transparent and zero expansion, Al2O3 / (Li2O+(1 / 2×(MgO+ZnO)) is preferably 3.0-8.0, 3.2-7.8, 3.4-7.6, 3.5-7.5, 3.7-7.5, 4.0-7.5, 4.3-7.5, 4.5-7.5, 4.8-7.5, 5.0-7.5, 5.5-7.3, 5.5-7.1, 5.5-7.0, 5.5-6.8, 5.5-6.7, 5.5-6.6 in terms of mass ratio, and particularly preferably 5.5-6.5.

[0084] Y2O3 is a component that reduces the viscosity of glass and improves the meltability and formability of glass. In addition, it is also a component used to increase the Young's modulus of crystallized glass, adjust the thermal expansion coefficient and refractive index. The content of Y2O3 is preferably 0-10%, 0-8%, 0-6%, 0-5%, 0-4.5%, 0-4%, 0-3.5%, 0-3%, 0-2.7%, 0-2.4%, 0-2.1%, 0-1.8%, 0-1.5%, and particularly preferably 0-1%. When the content of Y2O3 is too much, crystals containing Y are precipitated, the glass becomes easily devitrified, and the crystallized glass becomes easily broken. In addition, the ionic radius of the Y cation is larger than the constituent components of the main crystal, such as Li cations and Mg cations, and it is not easy to enter the crystallization, so the Y cation after crystallization is easy to remain in the residual glass. Therefore, when the content of Y2O3 is too much, there is a tendency that the refractive index difference between the crystalline phase and the residual glass is easy to be generated, and the crystallized glass is easy to be turbid. However, since Y2O3 is sometimes mixed as an impurity, if you want to completely remove Y2O3, there is a tendency that the raw material batch becomes expensive and the manufacturing cost increases. In order to suppress the increase in manufacturing cost, the lower limit of the Y2O3 content is preferably 0.0001% or more, 0.0003% or more, and particularly preferably 0.0005% or more.

[0085] In Li2O-Al2O3-SiO2 crystallized glass, Li cation, Mg cation, and Zn cation are components that are easily dissolved in β-quartz solid solution, and are considered to be components that contribute less to the increase in the refractive index of the residual glass after crystallization than Ba ​​cations. In addition, Li2O, MgO, and ZnO function as fluxes when vitrifying the raw materials, so it can be said that they are important components for manufacturing colorless and transparent crystallized glass at low temperatures. Li2O is a component necessary for achieving low expansion, and it is necessary to contain more than 1%. In order to achieve the desired thermal expansion coefficient, etc., it is necessary to contain the necessary amount of Li2O, but when the content of MgO and ZnO is increased accordingly, there is a concern that the viscosity of the glass will decrease excessively. When the low-temperature viscosity decreases excessively, the softening fluidity of the glass becomes too large during firing, and it is sometimes difficult to crystallize into the desired shape. In addition, when the high-temperature viscosity decreases excessively, although the thermal burden on the manufacturing equipment is reduced, the convection speed during heating becomes faster, and there is a concern that it is easy to physically erode the refractory. Therefore, it is preferred to control the content ratio of Li2O, MgO, and ZnO, and it is particularly preferred to control the total amount of MgO and ZnO relative to Li2O, which has a high function as a flux. For this purpose, (MgO+ZnO) / Li2O is preferably 0.394 or less, 0.393 or less, 0.392 or less, 0.391 or less in terms of mass ratio, and is particularly preferably reduced to 0.390 or less, or preferably 0.755 or more, 0.756 or more, 0.757 or more, 0.758 or more, and is particularly preferably increased to 0.759 or more.

[0086] B2O3 is a component that reduces the viscosity of glass and improves the solubility and formability of glass. In addition, it is also a component that can interfere with the ease of phase separation when forming crystal nuclei. The content of B2O3 is preferably 0-10%, 0-8%, 0-6%, 0-5%, 0-4.5%, 0-4%, 0-3.5%, 0-3%, 0-2.7%, 0-2.4%, 0-2.1%, 0-1.8%, and 0-1.5% is particularly preferred. When the content of B2O3 is too much, the amount of B2O3 evaporated during melting increases, and the environmental load increases. However, since B2O3 is easily mixed as an impurity, if B2O3 is to be completely removed, there is a tendency that the raw material batch becomes expensive and the manufacturing cost increases. In order to suppress the increase in manufacturing costs, B2O3 preferably contains more than 0.0001%, more than 0.0003%, and more preferably contains more than 0.0005%.

[0087] In Li2O-Al2O3-SiO2 crystallized glass, it is known that after a phase separation region is formed in the glass before a crystal nucleus is formed, a crystal nucleus composed of TiO2, ZrO2, etc. is formed in the phase separation region. Since SnO2, ZrO2, P2O5, TiO2, and B2O3 strongly interfere with the phase separation formation, SnO2+ZrO2+P2O5+TiO2+B2O3 is preferably 1.5-30%, 1.5-26%, 1.5-22%, 1.5-20%, 1.5-18%, 1.5-16%, 1.5-15%, 1.8-15%, 2.1-15%, 2.4-15%, 2.5-15%, 2.8-15%, 2.8-13%, 2.8-12%, 2.8-11%, 2.8- 10%, 3-9.5%, 3-9.2%, particularly preferably 3-9%, SnO2 / (SnO2+ZrO2+P2O5+TiO2+B2O3) is preferably 0.06 or more, 0.07 or more, 0.08 or more, 0.09 or more, 0.1 or more, 0.103 or more, 0.106 or more, 0.11 or more, 0.112 or more, 0.115 or more, 0.118 or more, 0.121 or more, 0.124 or more, 0.127 or more, 0.128 or more, particularly preferably 0.13 or more. When P2O5+B2O3+SnO2+TiO2+ZrO2 is too little, it becomes difficult to form a phase separation region and it becomes difficult to crystallize. When P2O5+B2O3+SnO2+TiO2+ZrO2 is too much and / or SnO2 / (SnO2+ZrO2+P2O5+TiO2+B2O3) is too small, the phase separation region becomes larger and the crystallized glass is prone to white turbidity. In addition, the upper limit of SnO2 / (SnO2+ZrO2+P2O5+TiO2+B2O3) is not particularly limited, but is less than 0.9 in reality.

[0088] Fe2O3 is a component that makes the coloring of glass stronger, and is particularly a component that makes the coloring significantly stronger due to the interaction with TiO2 and SnO2. The content of Fe2O3 is preferably below 0.10%, below 0.08%, below 0.06%, below 0.05%, below 0.04%, below 0.035%, below 0.03%, below 0.02%, below 0.015%, below 0.013%, below 0.012%, below 0.011%, below 0.01%, below 0.009%, below 0.008%, below 0.007%, below 0.006%, below 0.005%, below 0.004%, below 0.003%, and particularly preferably below 0.002%. However, since Fe2O3 is easily mixed in as an impurity, if Fe2O3 is to be completely removed, there is a tendency that the raw material batch becomes expensive and the manufacturing cost increases. In order to suppress an increase in manufacturing cost, the lower limit of the Fe2O3 content is preferably 0.0001% or more, 0.0002% or more, 0.0003% or more, 0.0005% or more, and particularly preferably 0.001% or more.

[0089] When titanium and iron coexist, ilmenite (FeTiO3)-like coloring sometimes occurs. In particular, in Li2O-Al2O3-SiO2-based crystallized glass, the titanium and iron components that have not been precipitated as crystal nuclei or main crystals after crystallization remain in the residual glass, which may promote the appearance of the above-mentioned coloring. Although the amount of these components can be reduced from the composition design, since TiO2 and Fe2O3 are easily mixed in as impurities, if they are to be completely removed, there is a tendency for the raw material batch to become expensive and the manufacturing cost to increase. Therefore, in order to suppress the manufacturing cost, TiO2 and Fe2O3 can be contained within the above-mentioned range, and in order to make the manufacturing cost lower, both components can be contained within the allowable range of coloring. In this case, TiO2 / (TiO2+Fe2O3) is preferably 0.001-0.999, 0.003-0.997, 0.005-0.995, 0.007-0.993, 0.009-0.991, 0.01-0.99, 0.1-0.9, 0.15-0.85, 0.2-0.8, 0.25-0.25, 0.3-0.7, 0.35-0.65 in terms of mass ratio, and 0.4-0.6 is particularly preferred. Thus, it is easy to obtain colorless and highly transparent crystallized glass at a low cost.

[0090] Pt is a component that can be mixed into glass in the state of ions, colloids, metals, etc., showing yellow to brown coloring. In addition, this tendency becomes significant after crystallization. Moreover, after careful exploration, it is found that when Pt is mixed, the nucleation and crystallization behavior of crystallized glass are affected, and sometimes turbidity is easy to occur. Therefore, the content of Pt is preferably less than 7ppm, less than 6ppm, less than 5ppm, less than 4ppm, less than 3ppm, less than 2ppm, less than 1.6ppm, less than 1.4ppm, less than 1.2ppm, less than 1ppm, less than 0.9ppm, less than 0.8ppm, less than 0.7ppm, less than 0.6ppm, less than 0.5ppm, less than 0.45ppm, less than 0.40ppm, less than 0.35ppm, particularly preferably less than 0.30ppm. Although the mixing of Pt should be avoided as much as possible, in the case of using ordinary melting equipment, it is sometimes necessary to use Pt parts in order to obtain homogeneous glass. Therefore, if you want to completely remove Pt, there is a tendency to increase manufacturing costs. In the case where there is no adverse effect on coloring, in order to suppress the increase in manufacturing cost, the lower limit of Pt content is preferably more than 0.0001ppm, more than 0.001ppm, more than 0.005ppm, more than 0.01ppm, more than 0.02ppm, more than 0.03ppm, more than 0.04ppm, more than 0.05ppm, more than 0.06ppm, particularly preferably more than 0.07ppm. In addition, in the case where coloring is allowed, Pt and ZrO2, TiO2 can also be used as the nucleating agent for promoting the precipitation of main crystallization. At this time, Pt can be used as nucleating agent alone, it is also possible to use it in combination with other components as nucleating agent. In addition, when Pt is used as nucleating agent, its form is not particularly limited (colloid, metal crystallization, etc.).

[0091] Rh is a component that can be mixed into glass in the state of ions, colloids, metals, etc., and can present yellow to brown coloring like Pt, and there is a tendency to make crystallized glass turbid. Therefore, the content of Rh is preferably below 7ppm, below 6ppm, below 5ppm, below 4ppm, below 3ppm, below 2ppm, below 1.6ppm, below 1.4ppm, below 1.2ppm, below 1ppm, below 0.9ppm, below 0.8ppm, below 0.7ppm, below 0.6ppm, below 0.5ppm, below 0.45ppm, below 0.40ppm, below 0.35ppm, particularly preferably below 0.30ppm. Although the mixing of Rh should be avoided as much as possible, in the case of using common melting equipment, it is sometimes necessary to use Rh parts in order to obtain homogeneous glass. Therefore, if you want to completely remove Rh, there is a tendency to increase manufacturing costs. In the case of no adverse effect on coloring, in order to suppress the increase in manufacturing cost, the lower limit of the content of Rh is preferably more than 0.0001ppm, more than 0.001ppm, more than 0.005ppm, more than 0.01ppm, more than 0.02ppm, more than 0.03ppm, more than 0.04ppm, more than 0.05ppm, more than 0.06ppm, particularly preferably more than 0.07ppm. In addition, in the case of allowing coloring, Rh and ZrO2, TiO2 can also be used as nucleating agents in the same manner. At this time, Rh can be used as nucleating agent alone, or it can be used as nucleating agent in combination with other components. In addition, when Rh is used as the nucleating agent for promoting the precipitation of main crystals, its form is not particularly limited (colloid, metal crystals, etc.).

[0092] In addition, Pt+Rh is preferably 9 ppm or less, 8 ppm or less, 7 ppm or less, 6 ppm or less, 5 ppm or less, 4.75 ppm or less, 4.5 ppm or less, 4.25 ppm or less, 4 ppm or less, 3.75 ppm or less, 3.5 ppm or less, 3.25 ppm or less, 3 ppm or less, 2.75 ppm or less, 2.5 ppm or less, 2.25 ppm or less, 2 ppm or less, 1.75 ppm or less, 1.5 ppm or less, 1.25 ppm or less, 1 ppm or less, 0.95 ppm or less, 0.9 ppm or less, 0.85 ppm or less, 0.8 ppm or less, 0.75 ppm or less, 0.7 ppm or less, 0.65 ppm or less, 0.60 ppm or less, 0.55 ppm or less, 0.50 ppm or less, 0.45 ppm or less, 0.40 ppm or less, 0.35 ppm or less, and particularly preferably 0.30 ppm or less. In addition, although the mixing of Pt and Rh should be avoided as far as possible, in the case of using common melting equipment, it is sometimes necessary to use Pt and Rh parts in order to obtain homogeneous glass. Therefore, if Pt and Rh are to be completely removed, there is a tendency for increased manufacturing costs. In the case of having no adverse effect on coloring, in order to suppress the increase in manufacturing costs, the lower limit of Pt+Rh is preferably more than 0.0001ppm, more than 0.001ppm, more than 0.005ppm, more than 0.01ppm, more than 0.02ppm, more than 0.03ppm, more than 0.04ppm, more than 0.05ppm, more than 0.06ppm, particularly preferably more than 0.07ppm.

[0093] In addition, when developing glass raw materials, various crucibles are usually used to make glasses of various compositions. Therefore, platinum and rhodium evaporated from the crucible are often present inside the electric furnace used for melting. It has been confirmed that Pt and Rh present inside the electric furnace will mix into the glass. In order to control the amount of Pt and Rh mixed, in addition to selecting the raw materials and crucible materials used, the content of Pt and Rh in the glass can be controlled by assembling a quartz cover on the crucible, lowering the melting temperature or shortening the melting time, etc.

[0094] MoO3 is a component that may be mixed from raw materials or melting parts, and is a component that promotes crystallization. The content of MoO3 is preferably 0-10%, 0-8%, 0-6%, 0-5%, 0-4.5%, 0-4%, 0-3.5%, 0-3%, 0-2.7%, 0-2.4%, 0-2.1%, 0-1.8%, 0-1.5%, 0-1%, 0-0.5%, 0-0.1%, 0-0.05%, 0-0.01%, particularly preferably 0-0.005%. When the content of MoO3 is too much, crystals containing Mo are precipitated, and glass becomes easy to devitrify, and crystallized glass becomes easy to break. In addition, the ionic radius of Mo cations is larger than the constituent components of the main crystal, Li cations, Mg cations, etc., and it is not easy to enter the crystallization, so the Mo cations after crystallization are easy to remain in the residual glass. Therefore, when MoO3 content is too much, there is the refractive index difference that is easy to produce crystalline phase and residual glass, and crystallized glass is easy to be turbid.And, when MoO3 content is too much, there is the concern that yellow coloration occurs.But, because MoO3 is sometimes mixed in as impurity, want to remove MoO3 completely, then there is the tendency that raw material batch becomes expensive, and manufacturing cost increases.In order to suppress manufacturing cost increase, MoO3 the lower limit of content is preferably more than 0%, more than 0.0001%, more than 0.0003%, particularly preferably more than 0.0005%.

[0095] As2O3 and Sb2O3 are highly toxic and may pollute the environment during the glass manufacturing process and the treatment of waste glass. Therefore, Sb2O3+As2O3 is preferably less than 2%, less than 1%, less than 0.7%, less than 0.7%, less than 0.65%, less than 0.6%, less than 0.55%, less than 0.5%, less than 0.45%, less than 0.4%, less than 0.35%, less than 0.3%, less than 0.25%, less than 0.2%, less than 0.15%, less than 0.1%, less than 0.05%, and it is particularly preferred that it is substantially free of (specifically less than 0.01% by mass). In addition, when As2O3 and Sb2O3 are contained, these components can also function as clarifiers and nucleating agents.

[0096] In the case of no adverse effect on coloring, in addition to the above-mentioned components, the Li2O-Al2O3-SiO2 system crystallized glass of the present invention can also contain trace components such as H2, CO2, CO, H2O, He, Ne, Ar, N2, etc. up to 0.1%. In addition, if Ag, Au, Pd, Ir, V, Cr, Sc, Ce, Pr, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Ac, Th, Pa, U, etc. are intentionally added to the glass, there is a tendency that the raw material cost becomes higher and the manufacturing cost becomes higher. On the other hand, when the glass containing Ag, Au, etc. is subjected to light irradiation or heat treatment, aggregates of these components can be formed, and crystallization is promoted using them as a starting point. In addition, since Pd, etc. have various catalyst effects, by containing them, it is possible to give glass or crystallized glass specific properties. In view of such circumstances, when the purpose is to impart crystallization promotion or other functions, the above-mentioned components can be contained in an amount of less than 1%, less than 0.5%, less than 0.3%, or less than 0.1%, respectively. When there is no such purpose, it is preferably less than 500 ppm, less than 300 ppm, or less than 100 ppm, and particularly preferably less than 10 ppm.

[0097] In the case of no adverse effect on coloring, the Li2O-Al2O3-SiO2 system crystallized glass of the present invention may also contain SO3, MnO, Cl2, La2O3, WO3, HfO2, Ta2O5, Nd2O3, Nb2O5, and RfO2 in total up to 10%. However, since the raw material batches of the above components are expensive and there is a tendency for the manufacturing cost to increase, they may not be added unless there is a special need. In particular, the raw material cost of HfO2 is relatively high, and Ta2O5 is a conflict mineral. Therefore, the total amount of these components is preferably 5% or less, 4% or less, 3% or less, 2% or less, 1% or less, 0.5% or less, 0.4% or less, 0.3% or less, 0.2% or less, 0.1% or less, 0.05% or less, less than 0.05%, 0.049% or less, 0.048% or less, 0.047% or less, 0.046% or less, and particularly preferably 0.045% or less.

[0098] In other words, the preferred composition range of the Li2O-Al2O3-SiO2 crystallized glass of the present invention is as follows: SiO2: 50-75%, Al2O3: 10-30%, Li2O: 1-8%, SnO2: 0-5%, ZrO2: 1-5%, MgO: 0-10%, P2O5: 0-5%, TiO2: 0% or more and less than 1.5%, (Li2O+Na2O+K2O) / ZrO2: 0-1.5, TiO2 / (TiO2+Fe2O3): 0.01-0.99, (MgO+ZnO) / Li2O: 0-0.8, β-OH value is 0.001-2 / mm; preferably, SiO2 :50~75%、Al2O3:10~30%、Li2O:1~8%、SnO2:more than 0% and less than 5%、ZrO2:1~5%、MgO:0~10%、P2O5:0~5%、TiO2:more than 0% and less than 1.5%、(Li2O+Na2O+K2O) / ZrO2:0~1.5、TiO2 / (TiO2+Fe2O3)0.01~0.99、(MgO+ZnO) / Li2O:0~0.8、(MgO+CaO+SrO+BaO) / (Li2O+Na2O+K2O):0~0.5、β-OH value is 0.001~2 / mm;more preferably as follows, SiO2 :50~75%、Al2O3:10~30%、Li2O:1~8%、SnO2:more than 0% and less than 5%、ZrO2:1~5%、MgO:0~10%、P2O5:0~5%、TiO2:more than 0% and less than 1.5%、(Li2O+Na2O+K2O) / ZrO2:0~1.5、TiO2 / (TiO2+Fe2O3):0.01~0.99、(MgO+ZnO) / Li2O:0~0.8、(MgO+CaO+SrO+BaO) / (Li2O+Na2O+K2O):0~0.5、(MgO+CaO+SrO+BaO) / ZrO2:0~2 , β-OH value is 0.001~2 / mm, more preferably as follows, SiO2: 50~75%, Al2O3: 10~30%, Li2O: 1~8%, SnO2: more than 0% and less than 5%, ZrO2: 1~5%, MgO: 0~10%, P2O5: 0~5%, TiO2: more than 0% and less than 1.5%, (Li2O+Na2O+K2O) / ZrO2: 0~1.5, TiO2 / (TiO2+Fe2O3): 0.01~0.99, (MgO+ZnO) / Li2O: 0~0.8, (MgO+CaO+SrO+BaO) / (Li2O+Na2O+K2O): 0~0.5, (MgO + CaO + SrO + BaO) / ZrO2: 0 ~ 2, SnO2 / (SnO2 + ZrO2 + P2O5 + TiO2 + B2O3): 0.06 ~ 0.9, β-OH value is 0.001 ~ 2 / mm; more preferably as follows, SiO2: 50 ~ 75%, Al2O3: 10 ~ 30%, Li2O: 1 ~ 8%, SnO2: more than 0% and less than 5%, ZrO2: 1 ~ 5%, MgO: 0 ~ 10%, P2O5: 0 ~ 5%, TiO2: more than 0% and less than 1.5%, (Li2O + Na2O + K2O) / ZrO2: 0 ~ 1.5, TiO2 / (TiO2 + Fe2O3) :0.01~0.99,(MgO+ZnO) / Li2O:0~0.8,(MgO+CaO+SrO+BaO) / (Li2O+Na2O+K2O):0~0.5,(MgO+CaO+SrO+BaO) / ZrO2:0~2,SnO2 / (SnO2+ZrO2+P2O5+TiO2+B2O3):0.06~0.9,Pt+Rh:0~5ppm,β-OH value is 0.001~2 / mm;More preferably, SiO2:50~75%,Al2O3:10~30%,Li2O:1~8%,SnO2:more than 0% and less than 5%,ZrO2:1~5% , MgO: 0~10%, P2O5: 0~5%, TiO2: 0% or more and less than 1.5%, (Li2O+Na2O+K2O) / ZrO2: 0~1.5, TiO2 / (TiO2+Fe2O3) 0.01~0.99, (MgO+ZnO) / Li2O: 0~0.394, (Mg O+CaO+SrO+BaO) / (Li2O+Na2O+K2O): 0~0.5, (MgO+CaO+SrO+BaO) / ZrO2: 0~2, SnO2 / (SnO2+ZrO2+P2O5+TiO2+B2O3): 0.06~0.9, Pt+Rh: 0~5ppm, β -OH value is 0.001-2 / mm; more preferably, SiO2: 50-75%, Al2O3: 10-30%, Li2O: 1-8%, SnO2: more than 0% and less than 5%, ZrO2: 1-5%, MgO: 0-10%, P2O5: 0-5%, TiO2: more than 0% and less than 1.5%, (Li2O+Na2O+K2O) / ZrO2: 0-1.5, TiO2 / (TiO2+Fe2O3): 0.01-0.99, (MgO+ZnO) / Li2O: 0-0.394, (MgO+CaO+SrO+BaO) / (Li2O+Na2O+K2O): 0-0.5, (MgO + CaO + SrO + BaO) / ZrO2: 0 ~ 2, SnO2 / (SnO2 + ZrO2 + P2O5 + TiO2 + B2O3): 0.06 ~ 0.9, Pt + Rh: 0 ~ 5ppm, HfO2 + Ta2O5: 0% or more and less than 0.05%, β-OH value is 0.001 ~ 2 / mm, Sb2O3 + As2O3: less than 0.7%; particularly preferably as follows, SiO2: 50 ~ 75%, Al2O3: 10 ~ 30%, Li2O: 1 ~ 8%, SnO2: more than 0% and less than 5%, ZrO2: 1 ~ 5%, MgO: 0 ~ 10%, P2O5: 0 ~ 5%, TiO2: 0% or more and less than 1.5%, (Li2O + Na2O + K2O) / ZrO2: 0 ~ 1 .5, TiO2 / (TiO2+Fe2O3): 0.01~0.99, (MgO+ZnO) / Li2O: 0~0.394, (MgO+CaO+SrO+BaO) / (Li2O+Na2O+K2O): 0~0.5, (MgO+CaO+SrO+BaO) / ZrO2: 0~2, SnO2 / (SnO2+ZrO2+P2O5+TiO2+B2O3): 0.06~0.9, Pt+Rh: 0~5ppm, HfO2+Ta2O5: more than 0% and less than 0.05%, β-OH value is 0.001~2 / mm, Sb2O3+As2O3: less than 0.7%, Al2O3 / (Li2O+(1 / 2×(MgO+ZnO))): 5.0~7.5. .

[0099] The Li2O-Al2O3-SiO2-based crystallized glass of the present invention having the above-mentioned composition tends to be colorless and transparent in appearance.

[0100] The β-OH value of the Li2O-Al2O3-SiO2 crystallized glass of the present invention is preferably 0.001 to 2 / mm, 0.01 to 1.5 / mm, 0.02 to 1.5 / mm, 0.03 to 1.2 / mm, 0.04 to 1.5 / mm, 0.05 to 1 / mm, 0.06 to 1 / mm, 0.07 to 1 / mm, 0.08 to 0.9 / mm, 0.08 to 0.85 / mm m, 0.08-0.8 / mm, 0.08-0.75 / mm, 0.08-0.7 / mm, 0.08-0.65 / mm, 0.08-0.6 / mm, 0.08-0.55 / mm, 0.08-0.54 / mm, 0.08-0.53 / mm, 0.08-0.52 / mm, 0.08-0.51 / mm, and particularly preferably 0.08-0.5 / mm. When the β-OH value is too small, the rate of nucleation in the crystallization process slows down, and the amount of nucleus generated tends to decrease. As a result, coarse crystals increase, the crystallized glass becomes turbid, and transparency is easily impaired. Although the reason for crystallization by making the β-OH value large is not completely clear, it can be expected that one of the reasons is that the β-OH group weakens the bonding of the glass skeleton and reduces the viscosity of the glass. In addition, it can be expected that one of the reasons is that the presence of β-OH groups in the glass makes it easier for components such as Zr that can function as crystal nuclei to move. When the β-OH value is too large, bubbles are easily generated at the interface between the glass and metal glassmaking furnace parts containing Pt or glassmaking furnace parts composed of refractory materials, which can easily reduce the quality of glass products. In addition, β-quartz solid solution crystals are easily converted into β-spodumene solid solution crystals, etc., which not only increases the crystal particle size, but also easily produces a refractive index difference inside the crystallized glass. As a result, the crystallized glass is prone to white turbidity. In addition, the β-OH value changes depending on the raw materials used, the melting atmosphere, the melting temperature, the melting time, etc., and the β-OH value can be adjusted by changing these conditions as needed.

[0101] The transmittance of the Li2O-Al2O3-SiO2 crystallized glass of the present invention is preferably 0% or more, 2.5% or more, 5% or more, 10% or more, 12% or more, 14% or more, 16% or more, 18% or more, 20% or more, 22% or more, 24% or more, 26% or more, 28% or more, 30% or more, 32% or more, 34% or more, 36% or more, 38% or more, 40% or more, 40.5% or more, 41% or more, 41.5% or more, 42% or more, 42.5% or more, 43% or more, 43.5% or more, 44% or more, 44.5% or more, and particularly preferably 45% or more. In applications requiring transmission of ultraviolet light, if the transmittance at a wavelength of 200nm is too low, there is a concern that the desired transmission capability cannot be obtained. In particular, when used for light cleaning using an ozone lamp or the like, medical use using an excimer laser, exposure use, or the like, it is preferred that the transmittance at a wavelength of 200 nm be high.

[0102] The transmittance of the Li2O-Al2O3-SiO2 crystallized glass of the present invention is preferably 0% or more, 1% or more, 2% or more, 3% or more, 4% or more, 5% or more, 6% or more, 7% or more, 8% or more, 9% or more, 10% or more, 10.5% or more, 11% or more, 11.5% or more, 12% or more, 12.5% ​​or more, 13% or more, 13.5% or more, 14% or more, 14.5% or more, 15% or more, 15.5% or more, and particularly preferably 16% or more. In applications where ultraviolet light needs to be transmitted, if the transmittance at a wavelength of 250nm is too low, there is a concern that the desired transmittance cannot be obtained. In particular, in the case of sterilization applications using low-pressure mercury lamps or processing applications using YAG lasers, it is preferred that the transmittance at a wavelength of 250nm is high.

[0103] The transmittance of the Li2O-Al2O3-SiO2 crystallized glass of the present invention is preferably 0% or more, 2.5% or more, 5% or more, 10% or more, 12% or more, 14% or more, 16% or more, 18% or more, 20% or more, 22% or more, 24% or more, 26% or more, 28% or more, 30% or more, 32% or more, 34% or more, 36% or more, 38% or more, 40% or more, 40.5% or more, 41% or more, 41.5% or more, 42% or more, 42.5% or more, 43% or more, 43.5% or more, 44% or more, 44.5% or more, and particularly preferably 45% or more. In particular, when used for UV curing / bonding / drying (UV curing), fluorescence detection of printed materials, insect attracting, etc., it is preferred that the transmittance at a wavelength of 300nm is high.

[0104] The transmittance of the Li2O-Al2O3-SiO2 system crystallized glass of the present invention when the thickness is 3 mm and the wavelength is 325 nm is preferably 0% or more, 2.5% or more, 5% or more, 10% or more, 12% or more, 14% or more, 16% or more, 18% or more, 20% or more, 22% or more, 24% or more, 26% or more, 28% or more, 30% or more, 32% or more, 34% or more, 36% or more, 38% or more, 40% or more, 42% or more, 44% or more, 46% or more, 48% or more, 50% or more, 52% or more, 54% or more, 56% or more, 57% or more, 58% or more, 59% or more, 60% or more, 61% or more, 62% or more, 63% or more, 64% or more, and particularly preferably 65% ​​or more. In particular, when used for UV curing, adhesion, drying (UV curing), fluorescence detection of printed materials, insect attracting, etc., it is preferred that the transmittance at a wavelength of 325 nm is high.

[0105] The transmittance of the Li2O-Al2O3-SiO2 crystallized glass of the present invention at a thickness of 3 mm and a wavelength of 350 nm is preferably 0% or more, 5% or more, 10% or more, 15% or more, 20% or more, 25% or more, 30% or more, 35% or more, 40% or more, 45% or more, 50% or more, 55% or more, 60% or more, 65% or more, 70% or more, 71% or more, 72% or more, 73% or more, 74% or more, 75% or more, 76% or more, 77% or more, 78% or more, 80% or more, 81% or more, 82% or more, 83% or more, and particularly preferably 84% or more. In particular, when used for processing using a YAG laser or the like, it is preferred that the transmittance at a wavelength of 350 nm is high.

[0106] The transmittance of the Li2O-Al2O3-SiO2 crystallized glass of the present invention is preferably 50% or more, 55% or more, 60% or more, 65% or more, 70% or more, 75% or more, 78% or more, 80% or more, 81% or more, 82% or more, 83% or more, and particularly preferably 84% or more when the thickness is 3 mm and the wavelength is 380 nm. If the transmittance at a wavelength of 380 nm is too low, the yellow coloring becomes stronger, and the transparency of the crystallized glass is reduced, and there is a concern that the desired transmission ability cannot be obtained.

[0107] The transmittance of the Li2O-Al2O3-SiO2 crystallized glass of the present invention is preferably 50% or more, 55% or more, 60% or more, 65% or more, 70% or more, 75% or more, 78% or more, 80% or more, 81% or more, 82% or more, 83% or more, 84% or more, 85% or more, 86% or more, 87% or more, and particularly preferably 88% or more when the transmittance at a wavelength of 800nm ​​is too low. It is easy to become green. In particular, when used for medical purposes such as vein authentication, it is preferred that the transmittance at a wavelength of 800nm ​​is high.

[0108] The transmittance of the Li2O-Al2O3-SiO2 crystallized glass of the present invention is preferably 50% or more, 55% or more, 60% or more, 65% or more, 70% or more, 72% or more, 74% or more, 76% or more, 78% or more, 80% or more, 81% or more, 82% or more, 83% or more, 84% or more, 85% or more, 86% or more, 87% or more, 88% or more, and particularly preferably 89% or more. If the transmittance at a wavelength of 1200nm is too low, it is easy to become green. In particular, when used for infrared communication purposes such as infrared cameras or remote controllers, it is preferred that the transmittance at a wavelength of 1200nm is high.

[0109] The transmittance change rate of the Li2O-Al2O3-SiO2 crystallized glass of the present invention before and after crystallization at a thickness of 3mm and a wavelength of 300nm is preferably 50% or less, 48% or less, 46% or less, 44% or less, 42% or less, 40% or less, 38% or less, 37.5% or less, 37% or less, 36.5% or less, 36% or less, 35.5% or less, and particularly preferably 35% or less. By reducing the transmittance change rate before and after crystallization, the transmittance after crystallization can be predicted and controlled before crystallization, and the desired transmittance can be easily obtained after crystallization. In addition, it is preferred that the transmittance change rate before and after crystallization is not only small at a wavelength of 300nm, but also small in the entire wavelength region.

[0110] The lightness L* of the Li2O-Al2O3-SiO2 crystallized glass of the present invention when the thickness is 3 mm is preferably 50 or more, 60 or more, 65 or more, 70% or more, 75 or more, 80 or more, 85 or more, 90 or more, 91 or more, 92 or more, 93 or more, 94 or more, 95 or more, 96 or more, 96.1 or more, 96.3 or more, and particularly preferably 96.5 or more. If the lightness L* is too small, there is a tendency to appear gray and dark regardless of the size of the chromaticity.

[0111] The chromaticity a* of the Li2O-Al2O3-SiO2 crystallized glass of the present invention when the thickness is 3 mm is preferably within ±5.0, within ±4.5, within ±4, within ±3.6, within ±3.2, within ±2.8, within ±2.4, within ±2, within ±1.8, within ±1.6, within ±1.4, within ±1.2, within ±1, within ±0.9, within ±0.8, within ±0.7, within ±0.6, and particularly preferably within ±0.5. When the lightness a* is too large in the negative direction, it tends to look green, and when it is too large in the positive direction, it tends to look red.

[0112] The chromaticity b* of the Li2O-Al2O3-SiO2 crystallized glass of the present invention when the thickness is 3 mm is preferably within ±5.0, within ±4.5, within ±4, within ±3.6, within ±3.2, within ±2.8, within ±2.4, within ±2, within ±1.8, within ±1.6, within ±1.4, within ±1.2, within ±1, within ±0.9, within ±0.8, within ±0.7, within ±0.6, and particularly preferably within ±0.5. When the lightness b* is too large in the negative direction, it tends to look blue, and when it is too large in the positive direction, it tends to look yellow.

[0113] The Li2O-Al2O3-SiO2 crystallized glass of the present invention has a strain point (equivalent to a viscosity of about 10 14.5 dPa·s) is preferably 600° C. or higher, 605° C. or higher, 610° C. or higher, 615° C. or higher, 620° C. or higher, 630° C. or higher, 635° C. or higher, 640° C. or higher, 645° C. or higher, 650° C. or higher, and particularly preferably 655° C. or higher. If the strain point is too low, the glass before crystallization is easily broken when it is molded.

[0114] The Li2O-Al2O3-SiO2 crystallized glass of the present invention has a slow cooling point (equivalent to a viscosity of about 10 13 dPa·s) is preferably 680° C. or higher, 685° C. or higher, 690° C. or higher, 695° C. or higher, 700° C. or higher, 705° C. or higher, 710° C. or higher, 715° C. or higher, 720° C. or higher, and particularly preferably 725° C. or higher. If the slow cooling point is too low, the glass before crystallization is easily broken when it is molded.

[0115] The Li2O-Al2O3-SiO2 crystallized glass of the present invention is easily crystallized by heat treatment, and therefore, it is not easy to measure the softening point (equivalent to a viscosity of about 10°C) of the glass as is the case with ordinary glass such as soda-lime glass. 7.6dPa·s). Therefore, in the Li2O-Al2O3-SiO2 system crystallized glass of the present invention, the temperature at which the slope of the thermal expansion curve of the glass before crystallization changes is used as the glass transition temperature as a substitute for the softening point. The Li2O-Al2O3-SiO2 system crystallized glass of the present invention, in the state of glass before crystallization, preferably has a glass transition temperature of 680°C or more, 685°C or more, 690°C or more, 695°C or more, 700°C or more, 705°C or more, 710°C or more, 715°C or more, 720°C or more, and particularly preferably 725°C or more. If the glass transition temperature is too low, the glass will flow excessively during crystallization and will be difficult to be formed into a desired shape.

[0116] The liquidus temperature of the Li2O-Al2O3-SiO2 system crystallized glass of the present invention is preferably 1540°C or less, 1535°C or less, 1530°C or less, 1525°C or less, 1520°C or less, 1515°C or less, 1510°C or less, 1505°C or less, 1500°C or less, 1495°C or less, 1490°C or less, 1485°C or less, 1480°C or less, 1475°C or less, 1470°C or less, 1465°C or less, 1460°C or less, 1455°C or less, 1450°C or less, 1445°C or less, 1440°C or less, 1435°C or less, 1430°C or less, 1425°C or less, 1420°C or less, 1415°C or less, and particularly preferably 1410°C or less. If the liquidus temperature is too high, devitrification is likely to occur during production. On the other hand, when the temperature is 1480°C or lower, it is easy to manufacture by a roll method or the like, when the temperature is 1450°C or lower, it is easy to manufacture by a casting method or the like, and when the temperature is 1410°C or lower, it is easy to manufacture by a melting method or the like.

[0117] The liquidus viscosity (logarithm of viscosity corresponding to liquidus temperature) of the Li2O-Al2O3-SiO2 system crystallized glass of the present invention is preferably 2.70 or more, 2.75 or more, 2.80 or more, 2.85 or more, 2.90 or more, 2.95 or more, 3.00 or more, 3.05 or more, 3.10 or more, 3.15 or more, 3.20 or more, 3.25 or more, 3.30 or more, 3.35 or more, 3.40 or more, 3.45 or more, 3.50 or more, 3.55 or more, 3.60 or more, 3.65 or more, and particularly preferably 3.70 or more. If the liquidus viscosity is too low, devitrification is easy during manufacture. On the other hand, when it is 3.40 or more, it is easy to manufacture by a roller method, when it is 3.50 or more, it is easy to manufacture by a casting method, and when it is 3.70 or more, it is easy to manufacture by a melting method, etc.

[0118] The Li2O-Al2O3-SiO2 system crystallized glass of the present invention preferably precipitates a β-quartz solid solution as the main crystal. By precipitating the β-quartz solid solution as the main crystal, the crystal grain size is easily reduced, so the crystallized glass is easy to transmit visible light and the transparency is easily improved. In addition, it is easy to make the thermal expansion coefficient of the glass close to zero. In addition, the Li2O-Al2O3-SiO2 system crystallized glass of the present invention precipitates a β-spodumene solid solution by heat treatment at a temperature higher than the crystallization condition for precipitating the β-quartz solid solution. The crystal grain size of the β-spodumene solid solution is easy to be larger than that of the β-quartz solid solution, and there is usually a tendency to be turbid when the crystallized glass is made, but by appropriately adjusting the glass composition and firing conditions, it is sometimes possible to reduce the refractive index difference between the crystalline phase containing the β-spodumene solid solution and the residual glass phase. In this case, the crystallized glass is unlikely to become turbid. The Li 2 O—Al 2 O 3 —SiO 2 -based crystallized glass of the present invention may contain crystals of β-spodumene solid solution or the like, as long as there is no adverse effect on coloration or the like.

[0119] The thermal expansion coefficient of the Li2O-Al2O3-SiO2 crystallized glass of the present invention at 30 to 380°C is preferably 30×10 -7 / ℃ below, 25×10 -7 / ℃ below, 20×10 -7 / ℃ below, 18×10 -7 / ℃ below, 16×10 -7 / ℃ below, 14×10 -7 / ℃ below, 13×10 -7 / ℃ below, 12×10 -7 / ℃ below, 11×10 -7 / ℃ below, 10×10 -7 / ℃ below, 9×10 -7 / ℃ below, 8×10 -7 / ℃ below, 7×10 -7 / ℃ below, 6×10 -7 / ℃ below, 5×10 -7 / ℃ below, 4×10 -7 / ℃ below, 3×10 -7 / °C or less, particularly preferably 2×10 -7 / °C or less. In addition, when dimensional stability and / or thermal shock resistance are particularly required, -5×10 -7 / ℃~5×10 -7 / ℃,-3×10 -7 / ℃~3×10 -7 / ℃,-2.5×10 -7 / ℃~2.5×10 -7 / ℃,-2×10-7 / ℃~2×10 -7 / ℃,-1.5×10 -7 / ℃~1.5×10 -7 / ℃,-1×10 -7 / ℃~1×10 -7 / °C, particularly preferably -0.5×10 -7 / ℃~0.5×10 -7 / ℃.

[0120] The thermal expansion coefficient of the Li2O-Al2O3-SiO2 crystallized glass of the present invention at 30 to 750°C is preferably 30×10 -7 / ℃ below, 25×10 -7 / ℃ below, 20×10 -7 / ℃ below, 18×10 -7 / ℃ below, 16×10 -7 / ℃ below, 14×10 -7 / ℃ below, 13×10 -7 / ℃ below, 12×10 -7 / ℃ below, 11×10 -7 / ℃ below, 10×10 -7 / ℃ below, 9×10 -7 / ℃ below, 8×10 -7 / ℃ below, 7×10 -7 / ℃ below, 6×10 -7 / ℃ below, 5×10 -7 / ℃ below, 4×10 -7 / °C or less, particularly preferably 3×10 -7 / °C or less. In addition, when dimensional stability and / or thermal shock resistance are particularly required, -15×10 -7 / ℃~15×10 -7 / ℃,-12×10 -7 / ℃~12×10 -7 / ℃,-10×10 -7 / ℃~10×10 -7 / ℃,-8×10 -7 / ℃~8×10 -7 / ℃,-6×10 -7 / ℃~6×10 -7 / ℃,-5×10 -7 / ℃~5×10 -7 / ℃,-4.5×10 -7 / ℃~4.5×10 -7 / ℃,-4×10 -7 / ℃~4×10 -7 / ℃,-3.5×10 -7 / ℃~3.5×10 -7 / ℃,-3×10 -7 / ℃~3×10 -7 / ℃,-2.5×10 -7 / ℃~2.5×10 -7 / ℃,-2×10 -7 / ℃~2×10 -7 / ℃,-1.5×10 -7 / ℃~1.5×10 -7 / ℃,-1×10 -7 / ℃~1×10 -7 / °C, particularly preferably -0.5×10 -7 / ℃~0.5×10 -7 / ℃.

[0121] The Young's modulus of the Li2O-Al2O3-SiO2 crystallized glass of the present invention is preferably 60 to 120 GPa, 70 to 110 GPa, 75 to 110 GPa, 75 to 105 GPa, 80 to 105 GPa, and particularly preferably 80 to 100 GPa. When the Young's modulus is too low or too high, the crystallized glass becomes easily broken.

[0122] The rigidity modulus of the Li2O-Al2O3-SiO2 crystallized glass of the present invention is preferably 25 to 50 GPa, 27 to 48 GPa, 29 to 46 GPa, and particularly preferably 30 to 45 GPa. When the rigidity modulus is too low or too high, the crystallized glass becomes easily broken.

[0123] The Poisson's ratio of the Li2O-Al2O3-SiO2 crystallized glass of the present invention is preferably 0.35 or less, 0.32 or less, 0.3 or less, 0.28 or less, 0.26 or less, and particularly preferably 0.25 or less. When the Poisson's ratio is too large, the crystallized glass becomes easily broken.

[0124] The density of the crystallizable glass before crystallization of the Li2O-Al2O3-SiO2-based crystallized glass of the present invention is preferably 2.30 to 2.60 g / cm 3 2.32~2.58g / cm 3 2.34~2.56g / cm 3 2.36~2.54g / cm 3 2.38~2.52g / cm 3 2.39~2.51g / cm 3 , particularly preferably 2.40 to 2.50 g / cm 3If the density of the crystallized glass is too low, the air permeability before crystallization becomes poor, and there is a concern that the glass may be contaminated during storage. If the density of the crystallized glass is too high, the weight per unit area becomes large, and handling becomes difficult.

[0125] The density of the Li2O-Al2O3-SiO2-based crystallized glass (after crystallization) of the present invention is preferably 2.40 to 2.80 g / cm 3 2.42~2.78g / cm 3 2.44~2.76g / cm 3 2.46~2.74g / cm 3 , particularly preferably 2.47 to 2.73 g / cm 3 . When the density of the crystallized glass is too small, there is a concern that the air permeability of the crystallized glass may deteriorate. When the density of the crystallized glass is too large, the weight per unit area increases, and the operation becomes difficult. In addition, the density of the crystallized glass (after crystallization) is an indicator for judging whether the glass is fully crystallized. Specifically, if it is the same glass, the greater the density (the greater the density difference between the original glass and the crystallized glass), the more progress the crystallization will make.

[0126] The density change rate of the Li2O-Al2O3-SiO2 system crystallized glass of the present invention is given by {(density after crystallization (g / cm 3 )-Density before crystallization (g / cm 3 )) / Density before crystallization (g / cm 3 )}×100(%), the density before crystallization is the density of the molten glass after being kept at 700°C for 30 minutes and then cooled to room temperature at 3°C / min, and the density after crystallization is the density after crystallization treatment under specified conditions. The density change rate is preferably 0.01-10%, 0.05-8%, 0.1-8%, 0.3-8%, 0.5-8%, 0.9-8%, 1-7.8%, 1-7.4%, 1-7%, 1.2-7%, 1.6-7%, 2-7%, 2-6.8%, 2-6.5%, 2-6.3%, 2-6.2%, 2-6.1%, 2-6%, 2.5-5%, 2.6-4.5%, 2.8-3.8%. By making the density change rate before and after crystallization small, the breakage rate after crystallization can be reduced, and the scattering of glass and glass matrix can be reduced, so that crystallized glass with high transmittance can be obtained. Especially in the area where the TiO2 content is less than 0.5% (especially less than 0.05%), not only can the coloring factors other than the absorption of TiO2 be reduced, but the scattering can also be significantly reduced, which helps to improve the transmittance.

[0127] The Li2O-Al2O3-SiO2 crystallized glass of the present invention may also be subjected to chemical strengthening. The treatment conditions of the chemical strengthening treatment may be appropriately selected in terms of the glass composition, crystallinity, type of molten salt, etc., and the treatment time and treatment temperature may be appropriately selected. For example, in order to facilitate chemical strengthening after crystallization, a glass composition containing more Na2O that can be contained in the residual glass may be selected, or the crystallinity may be intentionally reduced. In addition, the molten salt may contain alkali metals such as Li, Na, and K alone, or may contain multiple types. Moreover, not only conventional one-stage strengthening may be selected, but also multi-stage chemical strengthening may be selected. In addition, the Li2O content on the surface of the sample may be reduced compared to the inside of the sample by subjecting the Li2O-Al2O3-SiO2 crystallized glass of the present invention to chemical strengthening and other treatments before crystallization. When such a glass is crystallized, the crystallinity on the surface of the sample is lower than that on the inside of the sample, and the thermal expansion coefficient on the surface of the sample becomes relatively higher, so that the compressive stress caused by the thermal expansion difference can be introduced into the surface of the sample. In addition, when the crystallinity on the surface of the sample is low, the glass phase on the surface becomes more, and by selecting the glass composition, the chemical resistance and gas barrier properties can be improved.

[0128] Next, a method for producing the Li2O-Al2O3-SiO2 system crystallized glass of the present invention is described.

[0129] First, a batch of raw materials prepared in a manner to form a glass of the above composition is put into a glass melting furnace, and then melted at 1500-1750°C and formed. In addition, the glass can be melted by a flame melting method using a burner or the like, an electric melting method using electric heating, etc. In addition, it can also be melted by laser irradiation or melted by plasma. In addition, the shape of the sample can be made into a plate, fiber, film, powder, spherical, hollow, etc., without particular limitation.

[0130] Next, the obtained crystalline glass (glass that can be crystallized before crystallization) is heat treated to crystallize it. As the crystallization conditions, nucleation is first performed at 700-950°C (preferably 750-900°C) for 0.1-100 hours (preferably 1-60 hours), and then crystal growth is performed at 800-1050°C (preferably 800-1000°C) for 0.1-50 hours (preferably 0.2-10 hours). Thus, a transparent Li2O-Al2O3-SiO2 system crystallized glass in which β-quartz solid solution crystals are precipitated as the main crystals can be obtained. In addition, the heat treatment can be performed only at a certain specific temperature, or the temperature of more than two stages can be maintained for staged heat treatment, or heating can be performed while applying a temperature gradient.

[0131] In addition, crystallization can also be promoted by applying sound waves or irradiating electromagnetic waves. Moreover, the cooling rate of the crystallized glass reaching a high temperature can be carried out with a certain specific temperature gradient, or with a temperature gradient of more than two stages. When it is necessary to obtain sufficient thermal shock resistance, it is desired to control the cooling rate so as to fully relax the structure of the residual glass phase. About the average cooling rate from 800°C to 25°C, the part of the crystallized glass farthest from the surface thickness inside is preferably 3000°C / minute, 1000°C / minute or less, 500°C / minute or less, 400°C / minute or less, 300°C / minute or less, 200°C / minute or less, 100°C / minute or less, 50°C / minute or less, 25°C / minute or less, 10°C / minute or less, particularly preferably 5°C / minute or less. In addition, when long-term dimensional stability is required, it is more preferably 2.5°C / min or less, 1°C / min or less, 0.5°C / min or less, 0.1°C / min or less, 0.05°C / min or less, 0.01°C / min or less, 0.005°C / min or less, 0.001°C / min or less, 0.0005°C / min or less, and particularly preferably 0.0001°C / min or less. Except for the case where physical strengthening treatment is performed by air cooling, water cooling, etc., regarding the cooling rate of the crystallized glass, it is preferred that the cooling rate of the glass surface is close to the cooling rate of the thickness inside the farthest from the glass surface. The value of the cooling rate of the part of the thickness inside the farthest from the surface divided by the cooling rate of the surface is preferably 0.0001-1, 0.001-1, 0.01-1, 0.1-1, 0.5-1, 0.8-1, 0.9-1, and particularly preferably 1. By being close to 1, it is difficult to produce residual deformation at all positions of the crystallized glass sample, and it is easy to obtain long-term dimensional stability. In addition, the cooling rate of the surface can be estimated by contact temperature measurement or radiation thermometer, and the internal temperature can be estimated from the numerical data, the specific heat of the crystallized glass and the cooling medium, the thermal conductivity, etc. by placing the crystallized glass in a high-temperature state in the cooling medium to measure the heat and heat change rate of the cooling medium.

[0132] Example 1

[0133] The present invention will be described below based on examples, but the present invention is not limited to the following examples. Tables 1 to 42 show examples of the present invention (sample Nos. 1 to 131).

[0134] [Table 1]

[0135]

[0136] [Table 2]

[0137]

[0138] [Table 3]

[0139]

[0140] [Table 4]

[0141]

[0142] [Table 5]

[0143]

[0144] [Table 6]

[0145]

[0146] [Table 7]

[0147]

[0148] [Table 8]

[0149]

[0150] [Table 9]

[0151]

[0152] [Table 10]

[0153]

[0154] [Table 11]

[0155]

[0156] [Table 12]

[0157]

[0158] [Table 13]

[0159]

[0160] [Table 14]

[0161]

[0162] [Table 15]

[0163]

[0164] [Table 16]

[0165]

[0166] [Table 17]

[0167]

[0168] [Table 18]

[0169]

[0170] [Table 19]

[0171]

[0172] [Table 20]

[0173]

[0174] [Table 21]

[0175]

[0176] [Table 22]

[0177]

[0178] [Table 23]

[0179]

[0180] [Table 24]

[0181]

[0182] [Table 25]

[0183]

[0184] [Table 26]

[0185]

[0186] [Table 27]

[0187]

[0188] [Table 28]

[0189]

[0190] [Table 29]

[0191]

[0192] [Table 30]

[0193]

[0194] [Table 31]

[0195]

[0196] [Table 32]

[0197]

[0198] [Table 33]

[0199]

[0200] [Table 34]

[0201]

[0202] [Table 35]

[0203]

[0204] [Table 36]

[0205]

[0206] [Table 37]

[0207]

[0208] [Table 38]

[0209]

[0210] [Table 39]

[0211]

[0212] [Table 40]

[0213]

[0214] [Table 41]

[0215]

[0216] [Table 42]

[0217]

[0218] First, in order to obtain a glass having the composition recorded in each table, each raw material is mixed in the form of oxides, hydroxides, carbonates, nitrates, etc. to obtain a glass batch (the composition recorded in each table is the analysis value of the glass actually produced). The obtained glass batch is placed in a crucible containing platinum and rhodium, a reinforced platinum crucible without rhodium, a refractory crucible or a quartz crucible, and melted at 1600°C for 4 to 100 hours, then heated to 1650 to 1680°C and melted for 0.5 to 20 hours, roll-formed into a thickness of 5 mm, and then heat-treated at 700°C for 30 minutes in a slow cooling furnace, and the slow cooling furnace is cooled to room temperature at 100°C / h to obtain crystalline glass. In addition, the above-mentioned melting is carried out by the electric melting method widely used in the development of glass raw materials.

[0219] In addition, it was confirmed that the glass composition in contact with liquid or solid can be melted by laser irradiation using the glass composition of sample No. 27. It was also confirmed that the glass composition in contact with gas can be melted by laser while the glass sample is suspended by conveying gas from the periphery of the glass sample. It was also confirmed that the glass composition in contact with gas can be melted by laser. It was also confirmed that the glass composition can be formed into a hemispherical shape, a spherical shape, a fiber shape, a powder shape, etc. by pressing, re-stretching, spraying, etc. after being pre-molten into a melt using an electric furnace, etc. In addition, it was confirmed that the glass compositions of samples No. 28 to 49 can be melted by a continuous furnace combining burner heating and electric heating, and can be formed into a block shape, a peel shape, a hollow shape, etc. by a roller method, a film method, a rod method using medium heating, etc. In addition, it was confirmed that the glass composition of sample No. 15 can be formed into a thin plate shape, a tube shape, and a valve shape by an up-drawing method, a down-drawing method, a slit method, an overflow (melting) method, a hand-blowing method, etc. Next, using the glass composition of sample No. 59, it was confirmed that the glass composition could be solidified into a plate shape by pouring a molten glass onto a liquid having a higher specific gravity than sample No. 59 and then cooling it. In addition, the glass produced by any method could be crystallized under the conditions described in the table.

[0220] The Pt and Rh contents of the samples were analyzed using an ICP-MS device (Agilent 8800 manufactured by Agilent Technologies, Inc.). First, the prepared glass sample was crushed, moistened with pure water, and then dissolved by adding perchloric acid, nitric acid, sulfuric acid, hydrofluoric acid, etc. Thereafter, the Pt and Rh contents of the sample were measured using ICP-MS. The Pt and Rh contents of each measured sample were obtained based on a calibration curve prepared in advance using Pt and Rh solutions with known concentrations. The measurement mode was set to Pt: He gas / HMI (low mode), Rh: HEHe gas / HMI (medium mode), and the mass number was set to Pt: 198, Rh: 103. In addition, the Li2O content of the prepared sample was analyzed using an atomic absorption spectrometer (ContrAA600 manufactured by ANALYTIK JENA). The dissolution process of the glass sample and the use of the calibration curve are basically the same as those for Pt and Rh analysis. In addition, other components can be measured by ICP-MS or atomic absorption analysis in the same way as Pt, Rh, and Li2O, or a glass sample of known concentration previously analyzed by ICP-MS or atomic absorption analysis can be used as a calibration curve sample, and a calibration curve can be prepared by using an XRF analyzer (ZSX Primus IV manufactured by RIGAKU), and then the actual content of each component can be obtained from the XRF analysis value of the measured sample based on the calibration curve. When using XRF analysis, the tube voltage, tube current, exposure time, etc. are adjusted at any time according to the analyzed components.

[0221] For the crystalline glass recorded in each table, after heat treatment at 750-900°C for 0.75-60 hours to form nuclei, it is further heat treated at 800-1000°C for 0.25-3 hours to crystallize. After that, it is heat treated at 700°C for 30 minutes and cooled to room temperature at 100°C / h. For the obtained crystallized glass, the transmittance, diffuse transmittance, brightness, chromaticity, precipitated crystals, average crystallite size, thermal expansion coefficient, density, Young's modulus, rigidity modulus, Poisson's ratio and appearance are evaluated. In addition, for the crystalline glass before crystallization, the transmittance, brightness, chromaticity, etc. are measured by the same method as the crystallized glass. The β-OH value, viscosity and liquidus temperature are also measured for the crystalline glass.

[0222] Regarding transmittance, brightness and chromaticity, a crystallized glass plate with both sides optically polished to a thickness of 3 mm was evaluated by measurement using a spectrophotometer. The measurement was performed using a spectrophotometer V-670 manufactured by JASCO Corporation. Among them, the V-670 is equipped with an integrating sphere unit "ISN-723", and the measured transmittance is relative to the total light transmittance. In addition, the measurement wavelength range is 200 to 1500nm, the scanning speed is 200nm / minute, the sampling interval is 1nm, the bandwidth is set to 5nm in the wavelength range of 200 to 800nm, and is set to 20nm in the other wavelength ranges. Baseline correction (alignment 100%) and dark measurement (alignment 0%) are performed before the measurement. During the dark measurement, the barium sulfate plate attached to the ISN-723 is removed. Using the measured transmittance, the tristimulus values ​​XYZ are calculated based on JIS Z8781-42013 and the corresponding international standards, and the lightness and chromaticity (light source C / 10°) are calculated from each stimulus value. In addition, the diffuse transmittance of crystallized glass is also measured using the same model as above, with the barium sulfate plate attached to ISN-723 removed and the measurement sample set for measurement.

[0223] The precipitated crystals were evaluated using an X-ray diffractometer (Smart Lab, a fully automatic multi-purpose horizontal X-ray diffractometer manufactured by RIGAKU). The scanning mode was set to 2θ / θ measurement, the scanning type was continuous scanning, the scattering and divergence slit width was 1°, the light receiving slit width was 0.2°, the measurement range was 10-60°, the measurement interval was 0.1°, the scanning speed was 5° / minute, and the analysis software equipped with the same model component was used to evaluate the main crystal and the grain size. As the precipitated crystal species determined to be the main crystal, the β-quartz solid solution is shown in the table as "β-Q". In addition, the average crystallite size of the main crystal is calculated based on the Debye-Sherrer method using the measured X-ray diffraction peak. In addition, in the measurement used to calculate the average crystallite size, the scanning speed is 1° / minute.

[0224] The coefficient of thermal expansion is processed using The crystallized glass sample was evaluated from the average linear thermal expansion coefficient measured in the temperature range of 30 to 380°C and 30 to 750°C. The measurement was performed using a Dilatometer manufactured by NETZSCH. In addition, the thermal expansion curve in the temperature range of 30 to 750°C was measured using the same measuring instrument, and its inflection point was calculated to evaluate the glass transition point of the crystallizable glass before crystallization.

[0225] The Young's modulus, rigidity modulus and Poisson's ratio were measured at room temperature using a free resonance elastic modulus measuring apparatus (JE-RT3 manufactured by TECHNOLPLAS, Japan) on a plate sample (40 mm × 20 mm × 20 mm) whose surface was polished with a polishing liquid containing No. 1200 alumina powder.

[0226] The density was evaluated by the Archimedean method.

[0227] The strain point and the slow cooling point were evaluated using a fiber elongation method, wherein a fiber sample was prepared from crystalline glass by a hand-drawing method.

[0228] The β-OH value was determined by measuring the transmittance of the glass using FT-IR Frontier (manufactured by Perkin Elmer) using the following formula. The scanning speed was 100 μm / min and the sampling interval was 1 cm. -1 The number of scans was set to 10 for each measurement.

[0229] β-OH value = (1 / X)log10(T1 / T2)

[0230] X: Glass thickness (mm)

[0231] T1: at reference wavelength 3846cm -1 Transmittance (%)

[0232] T2: hydroxyl absorption wavelength 3600cm -1 Minimum transmittance near (%)

[0233] High temperature viscosity is evaluated by the platinum ball pull-up method. During the evaluation, the bulk glass sample is broken into appropriate sizes and placed in an alumina crucible in a manner that minimizes the introduction of bubbles. After that, the alumina crucible is heated to make the sample into a molten state, and the glass viscosity measurement values ​​at multiple temperatures are obtained. The constant of the Vogel-Fulcher formula is calculated, and a viscosity curve is prepared to calculate the temperature at each viscosity.

[0234] The liquidus temperature is evaluated by the following method. First, fill a platinum boat of about 120×20×10mm with glass powder of 300 to 500 microns, put it into an electric furnace and melt it at 1600°C for 30 minutes. After that, transfer it to an electric furnace with a linear temperature gradient and put it in for 20 hours to allow devitrification. After the test sample is air-cooled to room temperature, the devitrification precipitated at the interface between the platinum boat and the glass is observed, and the temperature at the devitrification precipitate is calculated based on the temperature gradient curve of the electric furnace, and it is used as the liquidus temperature. In addition, the obtained liquidus temperature is interpolated into the high-temperature viscosity curve of the glass, and the viscosity equivalent to the liquidus temperature is used as the liquidus viscosity. In addition, from the results of X-ray diffraction, composition analysis, etc. (Scanning electron microscope manufactured by Hitachi, Hitachi S3400N TyPE2, EMAX ENERGY EX250X manufactured by Horiba), it can be seen that the primary phase of the glass recorded in each table is mainly ZrO2.

[0235] The appearance was evaluated by visually confirming the color tone of the crystallized glass. In addition, visual inspection was performed on a white background and a black background, and observation was performed under indoor light and sunlight (implemented at 8:00, 12:00, and 16:00 on sunny and cloudy days in January, April, July, and October). The color tone was comprehensively judged from the results of each visual inspection.

[0236] As can be seen from Tables 1 to 42, the crystallized glasses of Samples No. 1 to 131 of the Examples are colorless and transparent, have high transmittance, have a thermal expansion coefficient of almost 0, and are sufficiently crystallized. Furthermore, the transmittance change rate before and after crystallization is small.

[0237] Figure 1 This is the transmittance curve of sample No. 27 before crystallization. Figure 2 This is the transmittance curve of sample No. 27 after crystallization. Figure 1 , 2 It can be seen that the transmittance change rate before and after crystallization is small.

[0238] In addition, the crystallized glass of sample No. 27 was immersed in a KNO3 melt at 475°C for 7 hours, and it was found that a compressive stress layer (compressive stress: 110 MPa, compression depth: 10 microns) was formed on the surface of the sample.

[0239] Example 2

[0240] Tables 43 and 44 show examples of the present invention (samples A to J). Table 45 shows comparative examples of the present invention (samples K to M).

[0241] [Table 43]

[0242]

[0243] [Table 44]

[0244]

[0245] [Table 45]

[0246]

[0247] Samples A to M shown in Tables 31, 32, and 33 were prepared in the same manner as in Example 1, and the β-OH values ​​before crystallization and the densities after crystallization were measured. The relationship between the β-OH values ​​and the densities of samples A to E is shown in FIG. Figure 3 The relationship between the β-OH value and density of samples F to J is shown in Figure 4 The relationship between the β-OH value and density of samples K to M is shown in Figure 5 .

[0248] from Figure 3 , 4 It can be seen that for crystallized glass with low TiO2 content, which is easy to become colorless and transparent, the larger the β-OH value, the higher the density and the more advanced the crystallization. Figure 5 It can be seen that for crystallized glass with high TiO2 content and easy to be colored yellow, crystallization is carried out to the same extent regardless of the β-OH value. This result clearly shows the effect of the present invention, that is, it is possible to efficiently provide a Li2O-Al2O3-SiO2 system crystallized glass that ensures transparency and suppresses yellow coloring caused by TiO2, Fe2O3, etc. In addition, this time, the representative embodiments of the present invention are recorded in Tables 31 and 32, but the same effect is also confirmed for other embodiments recorded in the present invention. In addition, in the embodiments recorded in Tables 31 and 32, the crystallization temperature is fixed to a certain fixed combination, but it is also confirmed that the same effect can be obtained for other combinations of crystallization temperatures. According to the desired firing time and the characteristics of the crystallized glass, the crystallization temperature can be changed arbitrarily.

[0249] Industrial Applicability

[0250] The Li2O-Al2O3-SiO2 crystallized glass of the present invention can be well used for front windows of oil stoves, wood stoves, etc., substrates for high-tech products such as color filters or image sensor substrates, positioning parts for firing electronic components, light diffusion plates, furnace core tubes for semiconductor manufacturing, masks for semiconductor manufacturing, optical lenses, dimensional measurement parts, communication parts, construction parts, chemical reaction containers, top plates for electromagnetic cooking, heat-resistant tableware, heat-resistant covers, window glass for fireproof doors, parts for astronomical telescopes, parts for cosmic optics, etc.

Claims

1. A Li2O-Al2O3-SiO2 crystallized glass, characterized in that: The crystallized glass contains, by mass%, more than 0% and less than 0.5% TiO2, 40-90% SiO2, 5-30% Al2O3, 1-10% Li2O, 0-20% SnO2, 1-20% ZrO2, 0-10% MgO, 0-10% P2O5, more than 0% and less than 0.01% Sb2O3+As2O3, and the β-OH value of the crystallized glass is 0.001-2 / mm.

2. The Li2O-Al2O3-SiO2 crystallized glass according to claim 1, characterized in that: In terms of mass %, it also contains 0-10% Na2O, 0-10% K2O, 0-10% CaO, 0-10% SrO, 0-10% BaO, 0-10% ZnO, and 0-10% B2O3.

3. The Li2O-Al2O3-SiO2 crystallized glass according to claim 1 or 2, characterized in that: It also contains less than 0.1% of Fe2O3 in terms of mass%.

4. The Li2O-Al2O3-SiO2 crystallized glass according to claim 1 or 2, characterized in that: In terms of mass ratio, SnO2 / (SnO2+ZrO2+P2O5+TiO2+B2O3) is greater than 0.

06.

5. The Li2O-Al2O3-SiO2 crystallized glass according to claim 1 or 2, characterized in that: In terms of mass ratio, Al2O3 / (SnO2+ZrO2) is less than 7.

1.

6. The Li2O-Al2O3-SiO2 crystallized glass according to claim 1 or 2, characterized in that: In terms of mass ratio, SnO2 / (SnO2+ZrO2) is 0.01 to 0.

99.

7. The Li2O-Al2O3-SiO2 crystallized glass according to claim 1 or 2, characterized in that: Contains less than 8% of Na2O+K2O+CaO+SrO+BaO in terms of mass%.

8. The Li2O-Al2O3-SiO2 crystallized glass according to claim 1 or 2, characterized in that: In terms of mass ratio, (SiO2+Al2O3) / Li2O is greater than 20.

9. The Li2O-Al2O3-SiO2 crystallized glass according to claim 1 or 2, characterized in that: In terms of mass ratio, (SiO2+Al2O3) / SnO2 is greater than 44.

10. The Li2O-Al2O3-SiO2 crystallized glass according to claim 1 or 2, characterized in that: In terms of mass ratio, (MgO+ZnO) / Li2O is less than 0.395 or exceeds 0.

754.

11. The Li2O-Al2O3-SiO2 crystallized glass according to claim 1 or 2, characterized in that: In terms of mass ratio, (Li2O+Na2O+K2O) / ZrO2 is less than 2.

0.

12. The Li2O-Al2O3-SiO2 crystallized glass according to claim 1 or 2, characterized in that: In terms of mass ratio, TiO2 / ZrO2 is 0.0001 to 5.

0.

13. The Li2O-Al2O3-SiO2 crystallized glass according to claim 1 or 2, characterized in that: In terms of mass ratio, TiO2 / (TiO2+Fe2O3) is 0.001 to 0.

999.

14. The Li2O-Al2O3-SiO2 crystallized glass according to claim 1 or 2, characterized in that: The appearance is colorless and transparent.

15. The Li2O-Al2O3-SiO2 crystallized glass according to claim 1 or 2, characterized in that: The transmittance at a thickness of 3 mm and a wavelength of 300 nm is 10% or more.

16. The Li2O-Al2O3-SiO2 crystallized glass according to claim 1 or 2, characterized in that: A β-quartz solid solution precipitated as the main crystal.

17. The Li2O-Al2O3-SiO2 crystallized glass according to claim 1 or 2, characterized in that: The thermal expansion coefficient at 30-380°C is 30×10 -7 / ℃ below.

18. The Li2O-Al2O3-SiO2 crystallized glass according to claim 1 or 2, characterized in that: In terms of mass ratio, Al2O3 / (Li2O+(1 / 2×(MgO+ZnO)) is 3.0 to 8.

0.

19. A Li2O-Al2O3-SiO2 crystallized glass, characterized in that: The crystallized glass contains, by mass%, more than 0% MoO3, 40-90% SiO2, 5-30% Al2O3, 1-10% Li2O, 0-20% SnO2, 1-20% ZrO2, 0-10% MgO, 0-10% P2O5, and more than 0% and less than 0.01% Sb2O3+As2O3, and the β-OH value of the crystallized glass is 0.001-0.5 / mm.

Citation Information

Patent Citations

  • Li2o-al2o3-sio2-based transparent crystallized glass for combustion apparatus window

    JP1989308845A

  • Li2o-al2o3-sio2 based glass ceramics

    JP1999228180A

  • Li2-al2o3-sio2 based glass ceramics

    JP1999228181A

  • Coloured fireplace panel with colour-neutral transmission characteristics

    CN109956668A

  • Li2O-Al2O3-SiO2 crystal galss and crystallizable glass thereof

    CN1285328A